Resin composition
By using an inorganic filler material with a high specific surface area and an appropriate amount of granular or non-grained elastomer resin composition, warping and other performance problems of printed wiring board insulation layer are solved, and efficient insulation and adhesion are achieved.
Patent Information
- Application Number
- CN202010612841.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-07-02
- Filing Date
- 2020-06-30
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2040-06-30
AI Technical Summary
The prior art is difficult to simultaneously suppress warping of the insulating layer of the printed wiring board, improve insulation reliability, adhesion and small-diameter through-hole formation.
A resin composition containing an epoxy resin, an inorganic filler material and a granular or non-grained elastomer is used to ensure that the specific surface area of the inorganic filler material reaches 10 m2/g or more, the content of the elastomer is less than 35 mass %, and the average particle size is less than 0.8 μm.
The warpage of the cured substance is effectively suppressed, and excellent insulation reliability, adhesion and small-diameter through-hole formation are achieved.
Smart Images

Figure BDA0002562735470000411
Abstract
Description
Technical Field
[0001] The present invention relates to a resin composition containing an epoxy resin and further to a cured product, a sheet-like laminate, a resin sheet, a printed wiring board, and a semiconductor device obtained by using the resin composition. Background Art
[0002] As a manufacturing technology for a printed wiring board, a manufacturing method based on a stacking method in which an insulating layer and a conductive layer are alternately stacked is known. In the manufacturing method based on the stacking method, generally, the insulating layer is formed by curing a resin composition.
[0003] Printed wiring boards are exposed to various environments such as high and low temperatures. Therefore, if the linear thermal expansion coefficient of the cured material used in the insulating layer is high, the insulating layer repeatedly expands and contracts, and cracks are generated due to its strain. As a method for suppressing the linear thermal expansion coefficient to a low level, a method of combining an inorganic filler in a cured material is known (Patent Document 1). However, if an inorganic filler is combined in a cured material, the elastic modulus becomes high, and it will be difficult to suppress warping.
[0004] In addition, when the cured material contains an inorganic filler, it is found that the adhesion between the conductor layer such as copper foil and the insulating layer is reduced. Recently, there is a demand for smaller semiconductor chip packages, and therefore, excellent adhesion is required.
[0005] In recent years, there has also been a demand for further improvement in the insulation reliability of the insulation layer and the small-diameter through-hole formability.
[0006] On the other hand, epoxy resin compositions containing an elastomer have been known so far (Patent Documents 2 and 3).
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Publication No. 2016-27097
[0010] Patent Document 2: Japanese Patent Application Publication No. 2019-38969
[0011] Patent document 3: International Publication No. 2008 / 153208. Summary of the invention
[0012] Problems to be solved by the invention
[0013] An object of the present invention is to provide a resin composition or the like which can suppress warping of a cured product and achieve excellent insulation reliability, adhesion, and small-diameter through-hole formability.
[0014] Means for solving problems
[0015] In order to solve the problem of the present invention, the present inventors have conducted intensive research and found that by using a composite material comprising (A) an epoxy resin, (B) an inorganic filler, and (C) a granular or non-granular elastomer, wherein the specific surface area of the component (B) is 10 m 2 / g or more, the content of component (C) is 35% by mass or less (the component ratio excluding component (B)), and the average particle size of component (C) is 0.8μm or less, so that the warping of the cured product can be suppressed and excellent insulation reliability, tightness, and small-diameter through-hole formation can be obtained, thereby completing the present invention.
[0016] That is, the present invention includes the following contents:
[0017] [1] A resin composition comprising (A) an epoxy resin, (B) an inorganic filler, and (C) a granular or non-granular elastomer,
[0018] The specific surface area of component (B) is 10m 2 / g or above,
[0019] When the nonvolatile components other than the component (B) in the resin composition are taken as 100% by mass, the content of the component (C) is 35% by mass or less.
[0020] When the component (C) is in a granular form, the average particle size of the component (C) is 0.8 μm or less;
[0021] [2] The resin composition according to [1] above, wherein the specific surface area of the component (B) is 20 m 2 / g or more;
[0022] [3] The resin composition according to [1] or [2] above, wherein the component (B) is silica;
[0023] [4] The resin composition according to any one of [1] to [3] above, wherein the content of the component (C) is 25% by mass or less when the non-volatile components other than the component (B) in the resin composition are taken as 100% by mass;
[0024] [5] The resin composition according to any one of [1] to [4] above, wherein the content of the component (C) is 1% by mass or more when the non-volatile components other than the component (B) in the resin composition are taken as 100% by mass;
[0025] [6] The resin composition according to any one of [1] to [5] above, wherein the component (C) is a granular elastomer.
[0026] The granular elastomer comprises at least one selected from styrene-butadiene rubber particles, isoprene rubber particles, butadiene rubber particles, chloroprene rubber particles, acrylonitrile-butadiene rubber particles, butyl rubber particles, ethylene-propylene rubber particles, polyurethane rubber particles, silicone rubber particles, chlorosulfonated polyethylene rubber particles, chlorinated polyethylene rubber particles, acrylic rubber particles, epichlorohydrin rubber particles, polysulfide rubber particles, and fluororubber particles;
[0027] [7] The resin composition according to any one of [1] to [5] above, wherein the component (C) is a non-granular elastomer.
[0028] The non-granular elastomer is a resin having at least one structure selected from the group consisting of a polybutadiene structure, a polysiloxane structure, a poly(meth)acrylate structure, a polyalkylene structure, a polyalkyleneoxy structure, a polyisoprene structure, a polyisobutylene structure, and a polycarbonate structure in the molecule;
[0029] [8] The resin composition according to [7] above, wherein the non-granular elastomer comprises a polybutadiene resin;
[0030] [9] The resin composition according to [8] above, wherein the non-granular elastomer comprises at least one selected from a polybutadiene resin containing a phenolic hydroxyl group and a polybutadiene resin containing an epoxy group;
[0031]
[10] The resin composition according to any one of [1] to [9] above, further comprising (D) a curing agent;
[0032]
[11] The resin composition according to
[10] above, wherein the component (D) comprises an active ester curing agent;
[0033]
[12] The resin composition according to
[10] or
[11] , wherein the content of the component (D) is 30% by mass or more when the non-volatile components other than the component (B) in the resin composition are taken as 100% by mass;
[0034]
[13] A cured product, which is a cured product of the resin composition described in any one of [1] to
[12] above;
[0035]
[14] A sheet-like laminated material comprising the resin composition described in any one of [1] to
[12] above;
[0036]
[15] A resin sheet comprising a support and a resin composition layer formed from the resin composition described in any one of [1] to
[12] above and disposed on the support;
[0037]
[16] A printed wiring board comprising an insulating layer formed from a cured product of the resin composition described in any one of [1] to
[12] above;
[0038]
[17] A semiconductor device comprising the printed wiring board described in
[16] above.
[0039] Effects of the Invention
[0040] According to the resin composition of the present invention, warping of a cured product can be suppressed, and excellent insulation reliability, adhesion, and small-diameter through-hole formability can be achieved. DETAILED DESCRIPTION
[0041] Hereinafter, the present invention will be described in detail according to its preferred embodiments. However, the present invention is not limited to the following embodiments and examples, and can be implemented with arbitrary changes within the scope of the claims of the present invention and their equivalents.
[0042] <Resin composition>
[0043] The resin composition of the present invention comprises (A) an epoxy resin, (B) an inorganic filler, and (C) a granular or non-granular elastomer, wherein the specific surface area of the component (B) is 10 m 2 / g or more, the content of component (C) is 35% by mass or less (the component ratio excluding component (B)), and the average particle size of component (C) is 0.8 μm or less. By using such a resin composition, the warping of the cured product can be suppressed, and excellent insulation reliability, adhesion, and small-diameter through-hole formation can be achieved.
[0044] For the resin composition of the present invention, in addition to (A) epoxy resin, (B) inorganic filler, and (C) granular or non-granular elastomer, any component may be included. As any component, for example, (D) curing agent, (E) curing accelerator, (F) flame retardant, (G) thermoplastic resin, (H) other additives, and (I) organic solvent can be cited. Hereinafter, each component included in the resin composition is described in detail.
[0045] <(A) Epoxy resin>
[0046] The resin composition of the present invention contains (A) an epoxy resin. The epoxy resin (A) refers to a resin having an epoxy group. However, the epoxy resin (A) does not contain a substance belonging to the component (C).
[0047] As (A) epoxy resin, for example, biphenylol type epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, bisphenol AF type epoxy resin, dicyclopentadiene type epoxy resin, trisphenol type epoxy resin, naphthol novolac type epoxy resin, phenol novolac type epoxy resin, tert-butyl-catechol type epoxy resin, naphthalene type epoxy resin, naphthol type epoxy resin, anthracene type epoxy resin, glycidylamine type epoxy resin, glycidyl ester type epoxy resin, cresol novolac type epoxy resin, biphenyl type epoxy resin, alicyclic epoxy resin, heterocyclic epoxy resin, spiro ring-containing epoxy resin, cyclohexane type epoxy resin, cyclohexanedimethanol type epoxy resin, naphthylene ether type epoxy resin, trimethylol type epoxy resin, tetraphenylethane type epoxy resin, etc. The epoxy resin may be used alone or in combination of two or more.
[0048] (A) The epoxy resin preferably has two or more epoxy groups in one molecule. When the non-volatile component of the epoxy resin is set to 100% by mass, it is preferred that at least 50% by mass is an epoxy resin having two or more epoxy groups in one molecule. Among them, the resin composition preferably contains in combination an epoxy resin that is liquid at a temperature of 20°C (hereinafter, also referred to as "liquid epoxy resin") and an epoxy resin that is solid at a temperature of 20°C (hereinafter, also referred to as "solid epoxy resin"). As a liquid epoxy resin, a liquid epoxy resin having two or more epoxy groups in one molecule is preferred. As a solid epoxy resin, a solid epoxy resin having three or more epoxy groups in one molecule is preferred.
[0049] As liquid epoxy resins, preferred are bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol AF type epoxy resins, naphthalene type epoxy resins, glycidyl ester type epoxy resins, glycidyl amine type epoxy resins, phenol novolac type epoxy resins, alicyclic epoxy resins having an ester skeleton, cyclohexane type epoxy resins, cyclohexanedimethanol type epoxy resins, and glycidyl amine type epoxy resins, and more preferred are naphthalene type epoxy resins and bisphenol A type epoxy resins.
[0050] Specific examples of liquid epoxy resins include "HP-4032", "HP-4032D", and "HP-4032SS" (naphthalene-type epoxy resins) manufactured by DIC Corporation; "828US", "jER828EL", "825", and "EPIKOTE828EL" (bisphenol A-type epoxy resins), "jER807", and "1750" (bisphenol F-type epoxy resins), "jER152" (phenol novolac-type epoxy resins), and "630" and "630LSD" (glycidylamine-type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "ZX1059" (a mixture of bisphenol A-type epoxy resin and bisphenol F-type epoxy resin) manufactured by NIPPON STEELChemical & Material Co., Ltd.; Nagase "EX-721" (glycidyl ester epoxy resin) manufactured by ChemteX; "CEL2021P" (alicyclic epoxy resin with ester skeleton) manufactured by Daicel Corporation; "ZX1658" and "ZX1658GS" (liquid 1,4-glycidylcyclohexane epoxy resin) manufactured by Nippon Steel Chemical Materials Co., Ltd.; "630LSD" (glycidylamine epoxy resin) manufactured by Mitsubishi Chemical Corporation; "EXA-850CRP" (bisphenol A epoxy resin) manufactured by DIC Corporation; "EP-3950S" and "EP-3980S" (glycidylamine epoxy resin) manufactured by ADEKA Corporation; "ELM-100H" (glycidylamine epoxy resin) manufactured by Sumitomo Chemical Co., Ltd., etc. These can be used alone or in combination of two or more.
[0051] As solid epoxy resins, preferred are biphenyl type epoxy resins, naphthalene type epoxy resins, naphthalene type tetrafunctional epoxy resins, cresol novolac type epoxy resins, dicyclopentadiene type epoxy resins, trisphenol type epoxy resins, naphthol type epoxy resins, biphenyl type epoxy resins, naphthylene ether type epoxy resins, anthracene type epoxy resins, bisphenol A type epoxy resins, bisphenol AF type epoxy resins, and tetraphenylethane type epoxy resins, and more preferred are biphenyl type epoxy resins and biphenyl type epoxy resins.
[0052] Specific examples of solid epoxy resins include "HP-4032H" (naphthalene-type epoxy resin) manufactured by DIC Corporation; "HP-4700" and "HP-4710" (naphthalene-type tetrafunctional epoxy resin) manufactured by DIC Corporation; "N-690" (cresol novolac-type epoxy resin) manufactured by DIC Corporation; "N-695" (cresol novolac-type epoxy resin) manufactured by DIC Corporation; "HP-7200", "HP-7200HH", "HP-7200HH" manufactured by DIC Corporation; "(dicyclopentadiene type epoxy resin); "EXA-7311", "EXA-7311-G3", "EXA-7311-G4", "EXA-7311-G4S", "HP6000L", "HP6000" (naphthyl ether type epoxy resin) manufactured by DIC Corporation; "EPPN-502H" (trisphenol type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "NC7000L" (naphthol novolac type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; " NC3000H", "NC3000", "NC3000L", "NC3100" (biphenyl type epoxy resin); "ESN475V" (naphthalene type epoxy resin) manufactured by Nippon Steel Chemicals; "ESN485" (naphthol novolac type epoxy resin) manufactured by Nippon Steel Chemicals; "YX4000H", "YX4000", "YL6121" (biphenyl type epoxy resin) manufactured by Mitsubishi Chemical; "YX4000HK" (biphenyl type epoxy resin) manufactured by Mitsubishi Chemical "YL7760" (bisphenol AF type epoxy resin) made by Mitsubishi Chemical Corporation; "YL7800" (fluorene type epoxy resin) made by Mitsubishi Chemical Corporation; "jER1010" (solid bisphenol A type epoxy resin) made by Mitsubishi Chemical Corporation; "jER1031S" (tetraphenylethane type epoxy resin) made by Mitsubishi Chemical Corporation, etc. These can be used alone or in combination of two or more.
[0053] When a liquid epoxy resin and a solid epoxy resin are used together as the component (A), the mass ratio of these (liquid epoxy resin:solid epoxy resin) is preferably in the range of 1:0.01 to 1:20, more preferably 1:0.1 to 1:10, and even more preferably 1:1 to 1:5.
[0054] The epoxy equivalent of component (A) is preferably 50 g / eq. to 5000 g / eq., more preferably 50 g / eq. to 3000 g / eq., further preferably 80 g / eq. to 2000 g / eq., and further more preferably 110 g / eq. to 1000 g / eq. By being in the above range, the crosslinking density of the cured product of the resin sheet becomes sufficient, and an insulating layer with a small surface roughness can be formed. The epoxy equivalent is the mass of a resin containing 1 equivalent of epoxy groups. The epoxy equivalent can be measured in accordance with JIS K7236.
[0055] The weight average molecular weight (Mw) of the component (A) is preferably 100 to 5,000, more preferably 250 to 3,000, and even more preferably 400 to 1,500. The weight average molecular weight of the epoxy resin is a polystyrene-equivalent weight average molecular weight measured by gel permeation chromatography (GPC).
[0056] The content of the epoxy resin (A) is not particularly limited. When the non-volatile components other than the inorganic filler (B) in the resin composition are set to 100% by mass, it is preferably 10% by mass or more, more preferably 20% by mass or more, further preferably 30% by mass or more, and particularly preferably 35% by mass or more. The upper limit of the content of the epoxy resin (A) is not particularly limited. When the non-volatile components other than the inorganic filler (B) in the resin composition are set to 100% by mass, it is preferably 90% by mass or less, more preferably 70% by mass or less, further preferably 60% by mass or less, and particularly preferably 50% by mass or less.
[0057] <(B) Inorganic fillers>
[0058] The resin composition of the present invention contains (B) an inorganic filler. In the present invention, the specific surface area of the (B) inorganic filler is 10 m 2 / g or more. (B) The inorganic filler is contained in the resin composition in the form of particles.
[0059] As the material of (B) inorganic filler, an inorganic compound is used. As the material of (B) inorganic filler, for example, silica, aluminum oxide, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate, calcium zirconate, zirconium phosphate, and zirconium phosphotungstate, etc., can be cited. Among these, from the viewpoint of significantly obtaining the desired effect of the present invention, silica is particularly preferred. As silica, for example, amorphous silica, fused silica, crystalline silica, synthetic silica, hollow silica, etc. can be cited. In addition, as silica, spherical silica is preferred. (B) The inorganic filler may be used alone or in combination of two or more in any ratio. When the resin composition of the present invention contains two or more inorganic fillers, the specific surface area of all the inorganic fillers combined is 10 m 2 / g or above.
[0060] (B) The specific surface area of the inorganic filler is 10m 2 / g or more, preferably 15 m / g from the viewpoint of significantly obtaining the desired effect of the present invention 2 / g or more, more preferably 18m 2 / g or more, particularly preferably 20 m 2 The upper limit of the specific surface area of the inorganic filler (B) is not particularly limited, and can be, for example, 500 m 2 / g or less, 300m 2 / g or less, 100m 2 / g or less, 50m 2 / g or less, 40m 2 / g or less, 30m 2 / g or less, 25m 2 (B) The specific surface area of the inorganic filler can be obtained by adsorbing nitrogen on the sample surface according to the BET method using a specific surface area measuring device (Macsorb HM-1210 manufactured by Mountech Co., Ltd.) and calculating the specific surface area by the BET multipoint method.
[0061] The average particle size of the inorganic filler (B) is not particularly limited, but is preferably 0.05 μm or more, more preferably 0.1 μm or more, further preferably 0.12 μm or more, and particularly preferably 0.14 μm or more. The upper limit of the average particle size of the inorganic filler (B) is not particularly limited, but is preferably 10.0 μm or less, 5.0 μm or less, more preferably 3.0 μm or less, 2.0 μm or less, further preferably 1.0 μm or less, 0.7 μm or less, and particularly preferably 0.5 μm or less, 0.3 μm or less.
[0062] (B) The average particle size of the particles of the inorganic filler can be measured by the laser diffraction-scattering method based on the Mie scattering theory. Specifically, it can be measured in the following manner: using a laser diffraction scattering particle size distribution measuring device, the particle size distribution of the particles is made on a volume basis, and the average particle size is measured from the particle size distribution as the median particle size. The measured sample can preferably use a product formed by dispersing the particles in a solvent such as water using ultrasound. As a laser diffraction scattering particle size distribution measuring device, "LA-500" manufactured by Horiba, Ltd., "SALD-2200" manufactured by Shimadzu Corporation, etc. can be used.
[0063] As (B) inorganic fillers, for example, there can be mentioned "UFP-20", "UFP-30", "SFP-20M" manufactured by DENKA Corporation; "Silfil NSS-3N", "Silfil NSS-4N", "Silfil NSS-5N" manufactured by Tokuyama Co., Ltd.; "SO-C1", "SO-E1", "YC100C", "YA050C", "YA010C" manufactured by Admatechs Co., Ltd.
[0064] It is preferred that the (B) inorganic filler material is surface treated with an appropriate surface treatment agent. By performing the surface treatment, the moisture resistance and dispersibility of the (B) inorganic filler material can be improved. Examples of the surface treatment agent include: vinyl-based silane coupling agents such as vinyltrimethoxysilane and vinyltriethoxysilane; epoxy-based silane coupling agents such as 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane; styrene-based silane coupling agents such as styryltrimethoxysilane; 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane; Methacrylic silane coupling agents such as acyloxypropyl trimethoxysilane, 3-methacryloxypropyl methyldiethoxysilane, and 3-methacryloxypropyl triethoxysilane; acrylic silane coupling agents such as 3-acryloxypropyl trimethoxysilane; N-2-(aminoethyl)-3-aminopropyl methyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyl trimethoxysilane, 3-aminopropyl trimethoxysilane, 3-aminopropyl triethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylene)propylamine , amino-based silane coupling agents such as N-phenyl-3-aminopropyltrimethoxysilane, N-phenyl-8-aminooctyltrimethoxysilane, and N-(vinylbenzyl)-2-aminoethyl-3-aminopropyltrimethoxysilane; isocyanurate-based silane coupling agents such as tris(trimethoxysilylpropyl)isocyanurate; urea-based silane coupling agents such as 3-ureidopropyltrialkoxysilane; mercapto-based silane coupling agents such as 3-mercaptopropylmethyldimethoxysilane and 3-mercaptopropyltrimethoxysilane; isocyanate-based silane coupling agents such as 3-isocyanatepropyltriethoxysilane ; 3-trimethoxysilylpropyl succinic anhydride and other acid anhydride silane coupling agents; silane coupling agents such as methyltrimethoxysilane, dimethyldimethoxysilane, phenyltrimethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, phenyltriethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, hexyltrimethoxysilane, hexyltriethoxysilane, octyltriethoxysilane, decyltrimethoxysilane, 1,6-bis(trimethoxysilyl)hexane, trifluoropropyltrimethoxysilane and other non-silane coupling-alkoxysilane compounds. In addition, the surface treatment agent may be used alone or in combination of two or more in any ratio.
[0065] The degree of surface treatment by the surface treatment agent can be evaluated by the carbon content per unit surface area of the (B) inorganic filler. From the viewpoint of improving the dispersibility of the (B) inorganic filler, the carbon content per unit surface area of the (B) inorganic filler is preferably 0.02 mg / m 2More preferably 0.1 mg / m 2 More than 0.2 mg / m 2 On the other hand, from the viewpoint of suppressing the increase of the melt viscosity of the resin composition and the melt viscosity in the form of a sheet, the carbon content is preferably 1 mg / m 2 Below, more preferably 0.8 mg / m 2 Below, particularly preferably 0.5 mg / m 2 the following.
[0066] The amount of carbon per unit surface area of the (B) inorganic filler can be measured after washing the surface-treated (B) inorganic filler with a solvent such as methyl ethyl ketone (hereinafter sometimes referred to as "MEK"). Specifically, a sufficient amount of methyl ethyl ketone can be mixed with the (B) inorganic filler surface-treated with a surface treatment agent, and ultrasonic washing can be performed at 25°C for 5 minutes. Then, the supernatant is removed, the solid component is dried, and the amount of carbon per unit surface area of the (B) inorganic filler is measured using a carbon analyzer. As a carbon analyzer, the "EMIA-320V" manufactured by Horiba, Ltd. can be used.
[0067] The content of the inorganic filler (B) in the resin composition is not particularly limited. When the non-volatile component in the resin composition is set to 100% by mass, it is preferably 10% by mass or more, more preferably 20% by mass or more, further preferably 30% by mass or more, and particularly preferably 40% by mass or more. The upper limit of the content of the inorganic filler (B) is not particularly limited. When the non-volatile component in the resin composition is set to 100% by mass, it is preferably 95% by mass or less, more preferably 90% by mass or less, further preferably 80% by mass or less, and particularly preferably 70% by mass or less.
[0068] <(C) Granular or non-granular elastomer>
[0069] The resin composition of the present invention contains (C) a granular or non-granular elastomer. In the present invention, the elastomer refers to a flexible resin, which is a granular resin component (granular elastomer) that maintains the form of particles in the resin composition, or an amorphous non-granular resin component (non-granular elastomer) that has a tendency to be mixed or dissolved in the resin composition, preferably a resin that exhibits rubber elasticity or a resin that reacts with other components to exhibit rubber elasticity. Examples of the resin that exhibits rubber elasticity include resins that exhibit an elastic modulus of less than 1 GPa when subjected to a tensile test at a temperature of 25° C. and a humidity of 40% RH according to Japanese Industrial Standards (JIS K7161).
[0070] The particulate elastomer is preferably in a spherical shape.
[0071] Examples of the particulate elastomer include diene rubber particles such as styrene-butadiene rubber (SBR) particles, isoprene rubber (IR) particles (including natural rubber (NR) particles), butadiene rubber (BR) particles, chloroprene rubber (CR) particles, acrylonitrile-butadiene rubber (NBR) particles (including hydrogenated nitrile rubber (HNBR) particles); butyl rubber (IIR) particles, ethylene-propylene rubber (EPM) particles (including ethylene-propylene-diene rubber (EPDM) particles), polyurethane rubber (U) particles (including polyester polyurethane rubber (AU) particles, polyether polyurethane rubber (EU) particles), silicone rubber (Q) particles (including methyl methacrylate particles), and the like. The rubber particles include non-diene rubber particles such as base silicone rubber (MQ) particles, vinyl-methyl silicone rubber (VMQ) particles, phenyl-methyl silicone rubber (PMQ) particles, fluorosilicone rubber (FVMQ) particles), chlorosulfonated polyethylene rubber (CSM) particles, chlorinated polyethylene rubber (CM) particles, acrylic rubber (ACM, ANM) particles, epichlorohydrin rubber (CO) particles (including epichlorohydrin-ethylene oxide rubber (ECO) particles), polysulfide rubber (T) particles, fluororubber (FKM) particles (including tetrafluoroethylene-propylene rubber (FEPM) particles, tetrafluoroethylene-perfluorovinyl ether rubber (FFKM) particles), and preferably polyurethane rubber particles.
[0072] As the granular elastomer, for example, there can be mentioned "MM-101SM (average particle size: 0.07 to 0.1 μm)", "MM-101SMA (average particle size: 0.1 to 0.2 μm)" (polyurethane rubber particles) manufactured by Negami Industries; "METABLEN W300A (average particle size: 0.1 μm)", "W450A (average particle size: 0.2 μm)" (acrylic rubber particles) manufactured by Mitsubishi Rayon; "XER-91 (average particle size: 0.5 μm)" (acrylonitrile-butadiene rubber particles) manufactured by JSR Corporation; "XSK-500 (average particle size: 0.5 μm)" (styrene-butadiene rubber particles) manufactured by JSR Corporation, etc. These can be used alone or in combination of two or more.
[0073] The average particle size of the granular elastomer is 0.8 μm or less, preferably 0.5 μm or less, more preferably 0.3 μm or less, and particularly preferably 0.2 μm or less from the viewpoint of significantly obtaining the desired effect of the present invention. The lower limit of the average particle size of the granular elastomer is not particularly limited, and may be, for example, 0.005 μm or more, 0.01 μm or more, 0.03 μm or more, 0.05 μm or more, etc. The average particle size of the granular elastomer used in the present invention can be measured by a dynamic light scattering method. For example, it can be measured in the following manner: the rubber particles are uniformly dispersed in an appropriate organic solvent by ultrasound or the like, and a particle size distribution of the rubber particles is prepared on a mass basis using a concentrated particle size analyzer (FPAR-1000; manufactured by Otsuka Electronics Co., Ltd.), and the mass-based median particle size (d50) is used as the average particle size.
[0074] The non-granular elastomer is preferably a resin having one or more structures selected from the group consisting of a polybutadiene structure, a polysiloxane structure, a poly(meth)acrylate structure, a polyalkylene structure, a polyalkyleneoxy structure, a polyisoprene structure, a polyisobutylene structure, and a polycarbonate structure in the molecule. From the viewpoint of obtaining a flexible material, a resin having one or more structures selected from the group consisting of a polybutadiene structure and a polycarbonate structure is more preferred, and a resin having a polybutadiene structure in the molecule, i.e., a polybutadiene resin is particularly preferred. It should be noted that the so-called "(meth)acrylate" refers to methacrylate and acrylate.
[0075] The polybutadiene structure includes not only a structure formed by polymerizing butadiene, but also a structure formed by hydrogenating the structure. In addition, the butadiene structure may be hydrogenated in part or in its entirety. In addition, the polybutadiene structure may be contained in the main chain or in the side chain in the non-granular elastomer.
[0076] Preferred examples of polybutadiene resins include: resins containing hydrogenated polybutadiene skeletons, polybutadiene resins containing hydroxyl groups, polybutadiene resins containing phenolic hydroxyl groups, polybutadiene resins containing carboxyl groups, polybutadiene resins containing acid anhydride groups, polybutadiene resins containing epoxy groups, polybutadiene resins containing isocyanate groups, polybutadiene resins containing carbamate groups, etc. Among them, polybutadiene resins containing phenolic hydroxyl groups and polybutadiene resins containing epoxy groups are more preferred. Here, the so-called "resin containing hydrogenated polybutadiene skeleton" refers to a resin in which at least a part of the polybutadiene skeleton is hydrogenated, and it is not necessarily a resin in which the polybutadiene skeleton is completely hydrogenated. As resins containing hydrogenated polybutadiene skeletons, for example, epoxy resins containing hydrogenated polybutadiene skeletons can be mentioned. As examples of preferred polybutadiene resins containing phenolic hydroxyl groups, for example, polybutadiene resins containing phenolic hydroxyl groups using hydroxyl-terminated polybutadiene, diisocyanate compounds, and resins containing phenolic hydroxyl groups as raw materials can be cited. Here, regarding hydroxyl-terminated polybutadiene and diisocyanate compounds, the same examples as those exemplified below can be cited. As resins containing phenolic hydroxyl groups, for example, cresol novolac resins can be cited.
[0077] Specific examples of the polybutadiene resin include: "PB-3600" (polybutadiene containing an epoxy group) manufactured by Daicel Corporation, "JP-100" and "JP-200" (polybutadiene containing an epoxy group) manufactured by Nippon Soda Co., Ltd., "Ricon 657" (polybutadiene containing an epoxy group) manufactured by Cray Valley Corporation, "Ricon 130MA8", "Ricon 130MA13", "Ricon 130MA20", "Ricon 131MA5", "Ricon 131MA10", "Ricon 131MA17", "Ricon 131MA20", "Ricon 131MA50", "Ricon 131MA10", "Ricon 131MA17", "Ricon 131MA20", "Ricon 131MA51", "Ricon 131MA11", "Ricon 131MA12", "Ricon 131MA13", "Ricon 131MA14", "Ricon 131MA150", "Ricon 131MA16", "Ricon 131MA171", "Ricon 131MA18", "Ricon 131MA19", "Ricon 131MA20", "Ricon 131MA21", "Ricon 131MA22", "Ricon 131MA23", "Ricon 131MA24", "Ricon 131MA25", "Ricon 131MA26", "Ricon 131MA27", "Ricon 131MA28", "Ricon 131MA29", "Ricon 131MA29", "Ricon 131MA21", "Ricon 131MA2 184MA6" (polybutadiene containing anhydride groups), "GQ-1000" (polybutadiene into which hydroxyl groups and carboxyl groups are introduced), "G-1000", "G-2000", "G-3000" (polybutadiene containing hydroxyl groups at both ends), "GI-1000", "GI-2000", "GI-3000" (hydrogenated polybutadiene containing hydroxyl groups at both ends), "PB3600", "PB4700" (polybutadiene skeleton epoxy compounds) manufactured by Daicel Corporation, "Epofriend A1005", "Epofriend A1010", "Epofriend A1020" (epoxy compounds of block copolymers of styrene, butadiene and styrene), "FCA-061L" (hydrogenated polybutadiene skeleton epoxy compound) manufactured by Nagase ChemteX Co., Ltd., "R-45EPT" (polybutadiene skeleton epoxy compound), etc.
[0078] In addition, as an example of a preferred polybutadiene resin, a linear polyimide (polyimide described in Japanese Unexamined Patent Publication No. 2006-37083 and International Publication No. 2008 / 153208) made of hydroxyl-terminated polybutadiene, a diisocyanate compound, and a polyacid or anhydride thereof can also be cited. The content (content) of the polybutadiene structure of the polyimide resin is preferably 60% to 95% by mass, and more preferably 75% to 85% by mass. The details of the polyimide resin can be referred to the records of Japanese Unexamined Patent Publication No. 2006-37083 and International Publication No. 2008 / 153208, and the contents are incorporated into this specification.
[0079] The number average molecular weight of the hydroxyl-terminated polybutadiene is preferably 500 to 5,000, and more preferably 800 to 3,500. The hydroxyl equivalent of the hydroxyl-terminated polybutadiene is preferably 250 to 5,000 g / eq., and more preferably 1,000 to 3,000 g / eq.
[0080] Examples of the diisocyanate compound include aromatic diisocyanates such as toluene-2,4-diisocyanate, toluene-2,6-diisocyanate, xylene diisocyanate, and diphenylmethane diisocyanate; aliphatic diisocyanates such as hexamethylene diisocyanate; and alicyclic diisocyanates such as isophorone diisocyanate. Among these, aromatic diisocyanates are preferred, and toluene-2,4-diisocyanate is more preferred.
[0081] Examples of the polybasic acid or its anhydride include ethylene glycol ditrimethylolpropane tetracarboxylic acid, pyromellitic acid, benzophenone tetracarboxylic acid, biphenyl tetracarboxylic acid, naphthalene tetracarboxylic acid, 5-(2,5-dioxotetrahydrofuranyl)-3-methyl-cyclohexene-1,2-dicarboxylic acid, 3,3'-4,4'-diphenylsulfone tetracarboxylic acid and their anhydrides, tribasic acids such as trimellitic acid and cyclohexanetricarboxylic acid and their anhydrides, 1,3,3a,4,5,9b-hexahydro-5-(tetrahydro-2,5-dioxo-3-furanyl)-naphtho(1,2-C)furan-1,3-dione and the like.
[0082] The polybutadiene resin may include a polystyrene structure having a structure obtained by polymerizing styrene.
[0083] Specific examples of resins having a polystyrene structure in the molecule, i.e., polystyrene resins, include: styrene-butadiene-styrene block copolymers (SBS), styrene-isoprene-styrene block copolymers (SIS), styrene-ethylene-butylene-styrene block copolymers (SEBS), styrene-ethylene-propylene-styrene block copolymers (SEPS), styrene-ethylene-ethylene-propylene-styrene block copolymers (SEEPS), styrene-butadiene-butylene-styrene block copolymers (SBBS), styrene-butadiene diblock copolymers, hydrogenated styrene-butadiene block copolymers, hydrogenated styrene-isoprene block copolymers, hydrogenated styrene-butadiene random copolymers, and the like.
[0084] The polystyrene resin may be a commercially available product, for example: hydrogenated styrene-based thermoplastic elastomer "H1041", "Tuftec H1043", "Tuftec P2000", "Tuftec MP10" (manufactured by Asahi Kasei Corporation); epoxidized styrene-butadiene thermoplastic elastomer "Epofriend AT501", "CT310" (manufactured by Daicel Corporation); modified styrene-based elastomer "SEPTON HG252" (manufactured by Kuraray Corporation) having a hydroxyl group; modified styrene-based elastomer "Tuftec N503M" having a carboxyl group, modified styrene-based elastomer "Tuftec N501" having an amino group, modified styrene-based elastomer "Tuftec M1913" having an acid anhydride group (manufactured by Asahi Kasei Chemicals Corporation); unmodified styrene-based elastomer "SEPTON S8104" (manufactured by Kuraray Corporation), etc. Component (C) may be used alone or in combination of two or more.
[0085] The polysiloxane structure is a structure containing a siloxane bond, and is contained in silicone rubber, for example. The polysiloxane structure may be contained in the main chain or in the side chain in the non-granular elastomer molecule.
[0086] Specific examples of the resin having a polysiloxane structure in the molecule, i.e., the polysiloxane resin, include: "SMP-2006", "SMP-2003PGMEA", "SMP-5005PGMEA" manufactured by Shin-Etsu Silicone Co., Ltd., and linear polyimide using amino-terminated polysiloxane and tetrabasic acid anhydride as raw materials (International Publication No. 2010 / 053185).
[0087] The poly(meth)acrylate structure is a structure formed by polymerizing acrylic acid or acrylic acid ester, and also includes a structure formed by polymerizing methacrylic acid or methacrylic acid ester. The (meth)acrylate structure may be contained in the main chain or in the side chain in the non-granular elastomer molecule.
[0088] Preferred examples of the resin having a poly(meth)acrylate structure in the molecule, i.e., the poly(meth)acrylate resin, include: a poly(meth)acrylate resin containing a hydroxyl group, a poly(meth)acrylate resin containing a phenolic hydroxyl group, a poly(meth)acrylate resin containing a carboxyl group, a poly(meth)acrylate resin containing an acid anhydride group, a poly(meth)acrylate resin containing an epoxy group, a poly(meth)acrylate resin containing an isocyanate group, a poly(meth)acrylate resin containing a carbamate group, and the like.
[0089] Specific examples of poly(meth)acrylate resins include: TEISANRESIN "SG-70L", "SG-708-6", "WS-023", "SG-700AS", "SG-280TEA" (carboxyl-containing acrylate copolymer resins, acid value of 5 to 34 mgKOH / g, weight average molecular weight of 400,000 to 900,000, Tg of -30°C to 5°C), "SG-80H", "SG-80H-3", "SG-P3" (epoxy-containing acrylate copolymer resins, epoxy equivalent of 4761 to 14285 g / eq, weight average molecular weight of 350,000) manufactured by Nagase ChemteX Co., Ltd. ~850,000, Tg is 11°C~12°C), "SG-600TEA", "SG-790" (hydroxyl-containing acrylate copolymer resin, hydroxyl value is 20~40mgKOH / g, weight average molecular weight is 500,000~1.2 million, Tg is -37°C~-32°C), "ME-2000", "W-116.3" (carboxyl-containing acrylate copolymer resin), "W-197C" (hydroxyl-containing acrylate copolymer resin), "KG-25", "KG-3000" (epoxy-containing acrylate copolymer resin) made by Negami Industries, Ltd., etc.
[0090] The polyalkylene structure preferably has a predetermined number of carbon atoms. The specific number of carbon atoms in the polyalkylene structure is preferably 2 or more, more preferably 3 or more, particularly preferably 5 or more, preferably 15 or less, more preferably 10 or less, particularly preferably 6 or less. In addition, the polyalkylene structure may be contained in the main chain or in the side chain in the non-granular elastomer molecule.
[0091] The polyalkyleneoxy structure preferably has a predetermined number of carbon atoms. The specific number of carbon atoms in the polyalkyleneoxy structure is preferably 2 or more, preferably 3 or more, more preferably 5 or more, preferably 15 or less, more preferably 10 or less, and particularly preferably 6 or less. The polyalkyleneoxy structure may be contained in the main chain or in the side chain in the non-granular elastomer molecule.
[0092] Specific examples of the resin having a polyalkylene structure in the molecule, i.e., the polyalkylene resin, and the resin having a polyalkyleneoxy structure in the molecule, i.e., the polyalkyleneoxy resin, include: "PTXG-1000" and "PTXG-1800" manufactured by Asahi Kasei Fibers Corporation, "YX-7180" (a resin containing an alkylene structure having an ether bond) manufactured by Mitsubishi Chemical Corporation, "EXA-4850-150", "EXA-4816", and "EXA-4822" manufactured by DIC Corporation, "EP-4000", "EP-4003", "EP-4010", and "EP-4011" manufactured by ADEKA Corporation, "BEO-60E" and "BPO-20E" manufactured by Shin Nippon Rika Co., Ltd., and "YL7175" and "YL7410" manufactured by Mitsubishi Chemical Corporation.
[0093] The polyisoprene structure may be contained in the main chain or in the side chain in the non-granular elastomer molecule. Specific examples of the resin having the polyisoprene structure in the molecule, i.e., the polyisoprene resin, include "KL-610" and "KL-613" manufactured by Kuraray Co., Ltd.
[0094] The polyisobutylene structure may be contained in the main chain or in the side chain in the non-granular elastomer molecule. Specific examples of the resin having the polyisobutylene structure in the molecule, i.e., the polyisobutylene resin, include "SIBSTAR-073T" (styrene-isobutylene-styrene triblock copolymer) and "SIBSTAR-042D" (styrene-isobutylene diblock copolymer) manufactured by KANEKA Corporation.
[0095] The polycarbonate structure may be contained in the main chain or in the side chain in the non-granular elastomer molecule.
[0096] Preferred examples of resins having a polycarbonate structure in their molecules, i.e., polycarbonate resins, include: polycarbonate resins containing hydroxyl groups, polycarbonate resins containing phenolic hydroxyl groups, polycarbonate resins containing carboxyl groups, polycarbonate resins containing acid anhydride groups, polycarbonate resins containing epoxy groups, polycarbonate resins containing isocyanate groups, polycarbonate resins containing carbamate groups, and the like.
[0097] Specific examples of the polycarbonate resin include "T6002" and "T6001" (polycarbonate diol) manufactured by Asahi Kasei Chemicals Corporation, and "C-1090", "C-2090" and "C-3090" (polycarbonate diol) manufactured by Kuraray Corporation.
[0098] In addition, as an example of a preferred polycarbonate resin, a linear polyimide made of a hydroxyl-terminated polycarbonate, a diisocyanate compound, and a polyacid or its anhydride as a raw material can also be cited. The linear polyimide has a carbamate structure and a polycarbonate structure. The content of the polycarbonate structure of the polyimide resin is preferably 60% to 95% by mass, and more preferably 75% to 85% by mass. The details of the polyimide resin can be referred to the record of International Publication No. 2016 / 129541, and the content is incorporated into this specification.
[0099] The number average molecular weight of the hydroxyl-terminated polycarbonate is preferably 500 to 5,000, more preferably 1,000 to 3,000. The hydroxyl equivalent of the hydroxyl-terminated polycarbonate is preferably 250 to 1,250.
[0100] The non-granular elastomer preferably further has an imide structure. The imide structure can improve the heat resistance of the non-granular elastomer and effectively improve the crack resistance.
[0101] The non-particulate elastomer may have any structure of linear, branched, or cyclic, but is preferably linear.
[0102] The non-granular elastomer preferably further has a functional group that can react with the component (A). The functional group also includes a reactive group that appears by heating. By providing the non-granular elastomer with a functional group, the mechanical strength of the cured product of the resin composition can be improved.
[0103] Examples of the functional group include a carboxyl group, a hydroxyl group, an acid anhydride group, a phenolic hydroxyl group, an epoxy group, an isocyanate group, and a carbamate group, etc. Among them, from the viewpoint of significantly obtaining the effect of the present invention, it is preferred that the functional group has one or more functional groups selected from a hydroxyl group, an acid anhydride group, a phenolic hydroxyl group, an epoxy group, an isocyanate group, and a carbamate group, and it is particularly preferred that the functional group has a phenolic hydroxyl group.
[0104] The non-particulate elastomer may be used alone or in combination of two or more.
[0105] The specific number average molecular weight Mn of the non-granular elastomer is preferably 500 or more, more preferably 800 or more, further preferably 1,000 or more, particularly preferably 1,200 or more, and preferably 100,000 or less, more preferably 50,000 or less, particularly preferably 10,000 or less. The number average molecular weight Mn of the non-granular elastomer is a number average molecular weight measured by GPC (gel permeation chromatography) in terms of polystyrene.
[0106] When the non-granular elastomer has a functional group, the functional group equivalent of the non-granular elastomer is preferably 100 g / eq. or more, more preferably 200 g / eq. or more, further preferably 1,000 g / eq. or more, particularly preferably 2,500 g / eq. or more, preferably 50,000 g / eq. or less, more preferably 30,000 g / eq. or less, further preferably 10,000 g / eq. or less, particularly preferably 5,000 g / eq. or less. The functional group equivalent is the number of grams of a resin containing 1 gram equivalent of a functional group. For example, the epoxy equivalent can be measured in accordance with JIS K7236. In addition, for example, the hydroxyl equivalent can be calculated by dividing the molecular weight of KOH by the hydroxyl value measured in accordance with JIS K1557-1.
[0107] (C) The glass transition temperature (Tg) of the granular or non-granular elastomer is preferably 20°C or lower, more preferably 10°C or lower, and further preferably 0°C or lower.
[0108] When the non-volatile components other than the inorganic filler (B) in the resin composition are set to 100% by mass, the content of the granular or non-granular elastomer (C) is 35% by mass or less, and from the viewpoint of significantly obtaining the desired effect of the present invention, it is preferably 30% by mass or less, more preferably 27% by mass or less, and particularly preferably 25% by mass or less. The lower limit of the content of the granular or non-granular elastomer (C) is not particularly limited, and when the non-volatile components other than the inorganic filler (B) in the resin composition are set to 100% by mass, it is preferably 0.1% by mass or more, more preferably 1% by mass or more, further preferably 3% by mass or more, and particularly preferably 5% by mass or more.
[0109] <(D) Curing agent>
[0110] The resin composition of the present invention may contain (D) a curing agent as an optional component (optional component). The (D) curing agent has a function of curing the (A) epoxy resin.
[0111] The (D) curing agent is not particularly limited, and examples thereof include phenol curing agents, naphthol curing agents, acid anhydride curing agents, active ester curing agents, benzoxazine curing agents, cyanate curing agents, and carbodiimide curing agents. The (D) curing agent preferably includes an active ester curing agent. The curing agent may be used alone or in combination of two or more.
[0112] As phenolic curing agent and naphthol curing agent, from the viewpoint of heat resistance and water resistance, preferably, phenolic curing agent with phenolic (novolac) structure or naphthol curing agent with phenolic structure is used. In addition, from the viewpoint of adhesion with the adherend, preferably, nitrogen-containing phenolic curing agent or nitrogen-containing naphthol curing agent is used, more preferably, phenolic curing agent containing triazine skeleton or naphthol curing agent containing triazine skeleton is used. Among them, from the viewpoint of highly satisfying heat resistance, water resistance, and adhesion, preferably, phenol novolac resin containing triazine skeleton is used. Specific examples of phenol-based curing agents and naphthol-based curing agents include: "MEH-7700", "MEH-7810", and "MEH-7851" manufactured by Meiwa Chemicals, "NHN", "CBN", and "GPH" manufactured by Nippon Kayaku Co., Ltd., "SN-170", "SN-180", "SN-190", "SN-475", "SN-485", "SN-495", "SN-375", and "SN-395" manufactured by Nippon Steel Chemicals Co., Ltd., and "LA-7052", "LA-7054", "LA-3018", "LA-3018-50P", "LA-1356", "TD2090", and "TD-2090-60M" manufactured by DIC Corporation.
[0113] Examples of the acid anhydride curing agent include curing agents having one or more acid anhydride groups in one molecule. Specific examples of the acid anhydride curing agent include phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, hydrogenated methylnadic anhydride, trialkyltetrahydrophthalic anhydride, dodecenylsuccinic anhydride, 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, trimellitic anhydride, pyromellitic anhydride, dicarboxylic anhydride, and the like. Benzophenone tetracarboxylic dianhydride, biphenyl tetracarboxylic dianhydride, naphthalene tetracarboxylic dianhydride, oxydiphthalic dianhydride, 3,3'-4,4'-diphenylsulfone tetracarboxylic dianhydride, 1,3,3a,4,5,9b-hexahydro-5-(tetrahydro-2,5-dioxo-3-furanyl)-naphtho[1,2-C]furan-1,3-dione, ethylene glycol bis(trimellitic anhydride ester), styrene-maleic acid resin obtained by copolymerization of styrene and maleic acid, etc. Examples of commercially available acid anhydride curing agents include "HNA-100" and "MH-700" manufactured by Shin Nippon Chemical Co., Ltd.
[0114] As active ester curing agent, there is no particular restriction, usually, it is preferred to use esters of phenolic esters, thiophenolic esters, N-hydroxylamine esters, heterocyclic hydroxy compounds, etc., which have ester groups with more than 2 high reactive activities in 1 molecule. The active ester curing agent is preferably obtained by the condensation reaction of carboxylic acid compounds and / or thiocarboxylic acid compounds with hydroxy compounds and / or thiol compounds. In particular, from the viewpoint of improving heat resistance, the active ester curing agent preferably obtained by carboxylic acid compounds and hydroxy compounds, more preferably the active ester curing agent obtained by carboxylic acid compounds and phenolic compounds and / or naphthol compounds. As carboxylic acid compounds, for example benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, pyromellitic acid, etc. can be cited. Examples of the phenol compound or naphthol compound include hydroquinone, resorcinol, bisphenol A, bisphenol F, bisphenol S, phenolphthalein, methylated bisphenol A, methylated bisphenol F, methylated bisphenol S, phenol, o-cresol, m-cresol, p-cresol, catechol, α-naphthol, β-naphthol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucinol, pyrogallol, dicyclopentadiene-type diphenol compounds, phenol novolac resins, etc. Here, the so-called "dicyclopentadiene-type diphenol compound" refers to a diphenol compound obtained by condensing two molecules of phenol on one molecule of dicyclopentadiene.
[0115] Specifically, active ester compounds containing a dicyclopentadiene-type diphenol structure, active ester compounds containing a naphthalene structure, active ester compounds containing acetylated products of phenol novolac, and active ester compounds containing benzoylated products of phenol novolac are preferred, and active ester compounds containing a naphthalene structure and active ester compounds containing a dicyclopentadiene-type diphenol structure are more preferred. The so-called "dicyclopentadiene-type diphenol structure" refers to a divalent structural unit composed of phenylene-dicyclopentalene-phenylene.
[0116] Commercially available active ester curing agents include: "EXB9451", "EXB9460", "EXB9460S", "HPC-8000", "HPC-8000H", "HPC-8000-65T", "HPC-8000H-65TM", "EXB-8000L", "EXB-8000L-65M", "EXB-8000L-65TM" (manufactured by DIC Corporation) as active ester compounds containing a dicyclopentadiene-type diphenol structure; "EXB9416-70BK", "HPC-8150-60T", "EXB-8150-60T" as active ester compounds containing a naphthalene structure; XB-8150-65T" (manufactured by DIC Corporation); "DC808" (manufactured by Mitsubishi Chemical Corporation) as an active ester compound containing an acetylated product of phenol novolac; "YLH1026" (manufactured by Mitsubishi Chemical Corporation) as an active ester compound containing a benzoylated product of phenol novolac; "DC808" (manufactured by Mitsubishi Chemical Corporation) as an active ester curing agent for an acetylated product of phenol novolac; "YLH1026" (manufactured by Mitsubishi Chemical Corporation), "YLH1030" (manufactured by Mitsubishi Chemical Corporation), and "YLH1048" (manufactured by Mitsubishi Chemical Corporation) as active ester curing agents for benzoylated products of phenol novolac; and the like.
[0117] Specific examples of the benzoxazine-based curing agent include “JBZ-OP100D” and “ODA-BOZ” manufactured by JFE Chemical Co., Ltd., “HFB2006M” manufactured by Showa High Molecular Co., Ltd., and “Pd” and “Fa” manufactured by Shikoku Chemical Industry Co., Ltd.
[0118] Examples of the cyanate curing agent include difunctional cyanate resins such as bisphenol A dicyanate, polyphenol cyanate (oligo(3-methylene-1,5-phenylene cyanate)), 4,4'-methylenebis(2,6-dimethylphenylcyanate), 4,4'-ethylenediphenyl dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyanate)phenylpropane, 1,1-bis(4-cyanatephenylmethane), bis(4-cyanate-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanatephenyl-1-(methylethylene))benzene, bis(4-cyanatephenyl)sulfide, and bis(4-cyanatephenyl)ether; polyfunctional cyanate resins derived from phenol novolac resins and cresol novolac resins; and prepolymers obtained by partially triazinizing these cyanate resins. Specific examples of cyanate curing agents include "PT30" and "PT60" manufactured by Lonza Japan (both are phenol novolac-type multifunctional cyanate resins), "BA230", "BA230S75" (prepolymers obtained by triazine-forming a part or all of bisphenol A dicyanate to form a trimer), etc.
[0119] Specific examples of the carbodiimide-based curing agent include "V-03" and "V-07" manufactured by Nisshinbo Chemical Co., Ltd.
[0120] When the resin composition contains (D) a curing agent, the amount ratio of the (A) epoxy resin to the (D) curing agent is preferably in the range of 1:0.2 to 1:2, more preferably 1:0.3 to 1:1.5, and even more preferably 1:0.4 to 1:1.2, in terms of [the total number of epoxy groups of the (A) epoxy resin]: [the total number of reactive groups of the (D) curing agent]. Here, the reactive group of the curing agent refers to an active hydroxyl group, an active ester group, etc., and varies depending on the type of the curing agent.
[0121] When the (D) curing agent includes an active ester curing agent, the content thereof is not particularly limited. When the total amount of the (D) curing agent is set to 100% by mass, it is preferably 10% by mass or more, more preferably 40% by mass or more, further preferably 60% by mass or more, and particularly preferably 70% by mass or more. The upper limit of the content of the active ester curing agent is not particularly limited. For example, when the total amount of the (D) curing agent is set to 100% by mass, it can be 100% by mass or less, 95% by mass or less, 90% by mass or less, 85% by mass or less, 80% by mass or less, etc.
[0122] When the resin composition contains (D) curing agent, its content is not particularly limited. When the non-volatile components other than (B) inorganic filler in the resin composition are set to 100% by mass, it is preferably 1% by mass or more, more preferably 10% by mass or more, further preferably 20% by mass or more, and particularly preferably 30% by mass or more. The upper limit of the content of (D) curing agent is not particularly limited. When the non-volatile components other than (B) inorganic filler in the resin composition are set to 100% by mass, it is preferably 80% by mass or less, more preferably 70% by mass or less, further preferably 60% by mass or less, and particularly preferably 50% by mass or less.
[0123] <(E) Curing accelerator>
[0124] The resin composition of the present invention may contain (E) a curing accelerator as an optional component. The (E) curing accelerator has a function of accelerating the curing of the (A) epoxy resin.
[0125] (E) curing accelerator is not particularly limited, and examples thereof include phosphorus curing accelerators, urea curing accelerators, amine curing accelerators, imidazole curing accelerators, guanidine curing accelerators, and metal curing accelerators. Among them, phosphorus curing accelerators, amine curing accelerators, imidazole curing accelerators, and metal curing accelerators are preferred, and amine curing accelerators are more preferred. One curing accelerator may be used alone, or two or more may be used in combination.
[0126] Phosphorus curing accelerators include, for example, tetrabutylphosphonium bromide, tetrabutylphosphonium chloride, tetrabutylphosphonium acetate, tetrabutylphosphonium decanoate, tetrabutylphosphonium laurate, bis(tetrabutylphosphonium)pyromellitic acid salt, tetrabutylphosphonium hexahydrophthalate, tetrabutylphosphonium cresol novolac resin trimer salt, di-tert-butylmethylphosphonium tetraphenylborate and other aliphatic phosphonium salts; methyltriphenylphosphonium bromide, ethyltriphenylphosphonium bromide, propyltriphenylphosphonium bromide, butyltriphenylphosphonium bromide, benzyltriphenylphosphonium chloride, tetraphenylphosphonium bromide, p-tolyltriphenylphosphonium tetra-p-tolylborate , tetraphenylphosphonium tetraphenylborate, tetraphenylphosphonium tetra-p-tolylborate, triphenylethylphosphonium tetraphenylborate, tris(3-methylphenyl)ethylphosphonium tetraphenylborate, tris(2-methoxyphenyl)ethylphosphonium tetraphenylborate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, butyltriphenylphosphonium thiocyanate and other aromatic phosphine-borane complexes; triphenylphosphine-p-benzoquinone addition reactants and other aromatic phosphine-quinone addition reactants; tributylphosphine, tri-tert-butylphosphine, trioctylphosphine, di-tert-butyl(2-butenyl)phosphine aliphatic phosphines such as di-tert-butyl (3-methyl-2-butenyl) phosphine and tricyclohexyl phosphine; dibutylphenyl phosphine, di-tert-butylphenyl phosphine, methyl diphenyl phosphine, ethyl diphenyl phosphine, butyl diphenyl phosphine, diphenylcyclohexyl phosphine, triphenyl phosphine, tri-o-tolyl phosphine, tri-m-tolyl phosphine, tri-p-tolyl phosphine, tri(4-ethylphenyl)phosphine, tri(4-propylphenyl)phosphine, tri(4-isopropylphenyl)phosphine, tri(4-butylphenyl)phosphine, tri(4-tert-butylphenyl)phosphine, tri(2,4-dimethylphenyl)phosphine, tri(2,5-dimethylphenyl)phosphine, tri(2,6-dimethylphenyl)phosphine )phosphine, tri(3,5-dimethylphenyl)phosphine, tri(2,4,6-trimethylphenyl)phosphine, tri(2,6-dimethyl-4-ethoxyphenyl)phosphine, tri(2-methoxyphenyl)phosphine, tri(4-methoxyphenyl)phosphine, tri(4-ethoxyphenyl)phosphine, tri(4-tert-butoxyphenyl)phosphine, diphenyl-2-pyridylphosphine, 1,2-bis(diphenylphosphino)ethane, 1,3-bis(diphenylphosphino)propane, 1,4-bis(diphenylphosphino)butane, 1,2-bis(diphenylphosphino)acetylene, 2,2'-bis(diphenylphosphino)diphenyl ether and the like.
[0127] Examples of the urea curing accelerator include 1,1-dimethylurea; aliphatic dimethylureas such as 1,1,3-trimethylurea, 3-ethyl-1,1-dimethylurea, 3-cyclohexyl-1,1-dimethylurea, and 3-cyclooctyl-1,1-dimethylurea; 3-phenyl-1,1-dimethylurea, 3-(4-chlorophenyl)-1,1-dimethylurea, 3-(3,4-dichlorophenyl)-1,1-dimethylurea, 3-(3-chloro-4-methylphenyl)-1,1-dimethylurea, 3-(2-methylphenyl)-1,1-dimethylurea, 3-(4-methylphenyl)-1,1-dimethylurea, 3-(3,4-dimethylphenyl)-1, Aromatic dimethyl urea such as 1-dimethyl urea, 3-(4-isopropylphenyl)-1,1-dimethyl urea, 3-(4-methoxyphenyl)-1,1-dimethyl urea, 3-(4-nitrophenyl)-1,1-dimethyl urea, 3-[4-(4-methoxyphenoxy)phenyl]-1,1-dimethyl urea, 3-[4-(4-chlorophenoxy)phenyl]-1,1-dimethyl urea, 3-[3-(trifluoromethyl)phenyl]-1,1-dimethyl urea, N,N-(1,4-phenylene)bis(N',N'-dimethyl urea), N,N-(4-methyl-1,3-phenylene)bis(N',N'-dimethyl urea) [toluenebisdimethyl urea], and the like.
[0128] Examples of the amine curing accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine (DMAP), benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, and 1,8-diazabicyclo(5,4,0)-undecene, and 4-dimethylaminopyridine is preferred.
[0129] Examples of the imidazole curing accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole trimellitate, 1-cyanoethyl-2-phenylimidazole trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1' imidazole compounds such as 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, 2-phenylimidazoline, and adducts of imidazole compounds with epoxy resins.
[0130] As the imidazole-based curing accelerator, a commercially available item may be used, and examples thereof include "P200-H50" manufactured by Mitsubishi Chemical Corporation.
[0131] Examples of the guanidine curing accelerator include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1-methylbiguanidine, 1-ethylbiguanidine, 1-n-butylbiguanidine, 1-n-octadecylbiguanidine, 1,1-dimethylbiguanidine, 1,1-diethylbiguanidine, 1-cyclohexylbiguanidine, 1-allylbiguanidine, 1-phenylbiguanidine, and 1-(o-tolyl)biguanidine.
[0132] As metal curing accelerators, organic metal complexes or organic metal salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin can be cited. As specific examples of organic metal complexes, organic cobalt complexes such as cobalt acetylacetonate (II), cobalt acetylacetonate (III), organic copper complexes such as copper acetylacetonate (II), organic zinc complexes such as zinc acetylacetonate (II), organic iron complexes such as iron acetylacetonate (III), organic nickel complexes such as nickel acetylacetonate (II), and organic manganese complexes such as manganese acetylacetonate (II) can be cited. As organic metal salts, for example, zinc octoate, tin octoate, zinc naphthenate, cobalt naphthenate, tin stearate, zinc stearate, etc. can be cited.
[0133] When the resin composition contains (E) a curing accelerator, its content is not particularly limited. When the non-volatile components other than (B) an inorganic filler in the resin composition are set to 100% by mass, it is preferably 0.001% by mass or more, more preferably 0.01% by mass or more, further preferably 0.05% by mass or more, and particularly preferably 0.1% by mass or more. The upper limit of the content of the (E) curing accelerator is not particularly limited. When the non-volatile components other than (B) an inorganic filler in the resin composition are set to 100% by mass, it is preferably 5% by mass or less, more preferably 1% by mass or less, further preferably 0.5% by mass or less, and particularly preferably 0.3% by mass or less.
[0134] <(F) Flame retardant>
[0135] The resin composition of the present invention may include (F) a flame retardant as an optional component. Examples of the (F) flame retardant include phosphorus-based flame retardants such as phosphazene compounds, phosphates, phosphinates, and phosphinates; nitrogen-based flame retardants such as aliphatic amine compounds, aromatic amine compounds, nitrogen-containing heterocyclic compounds, and urea compounds; inorganic flame retardants such as antimony trioxide, antimony pentoxide, and sodium antimonate; halogen-based flame retardants such as brominated polycarbonate resins, brominated epoxy resins, brominated phenoxy resins, brominated polyphenylene ether resins, brominated polystyrene resins, and brominated benzyl polyacrylate resins. Among them, phosphorus-based flame retardants are preferred. The (F) flame retardant may be used alone or in combination of two or more.
[0136] Specific examples of (F) flame retardants include: "SPH-100", "SPS-100", "SPB-100", "SPE-100" (phosphazene compounds) manufactured by Otsuka Chemical Co., Ltd.; "FP-100", "FP-110", "FP-300", "FP-400" (phosphazene compounds) manufactured by Fushimi Pharmaceutical Co., Ltd.; "HCA-HQ" (phosphinate) manufactured by Sanko Co., Ltd.; "PX-200", "PX-201", "PX-202", "CR-733S", "CR-741", "CR-747" (phosphate esters) manufactured by Daihachi Chemical Industry Co., Ltd.
[0137] When the resin composition contains (F) a flame retardant, its content is not particularly limited. When the non-volatile components other than (B) an inorganic filler in the resin composition are set to 100% by mass, it is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, further preferably 0.5% by mass or more, and particularly preferably 1% by mass or more. The upper limit of the content of the (F) flame retardant is not particularly limited. When the non-volatile components other than (B) an inorganic filler in the resin composition are set to 100% by mass, it is preferably 30% by mass or less, more preferably 10% by mass or less, further preferably 5% by mass or less, and particularly preferably 3% by mass or less.
[0138] <(G) Thermoplastic resin>
[0139] The resin composition of the present invention may contain (G) a thermoplastic resin as an optional component. The (G) thermoplastic resin here is a thermoplastic resin that does not belong to the (C) component.
[0140] (G) Thermoplastic resins include, for example, phenoxy resins, polyvinyl acetal resins, polyolefin resins, polyimide resins, polyamide-imide resins, polyetherimide resins, polysulfone resins, polyethersulfone resins, polyphenylene ether resins, polyetheretherketone resins, polyester resins, etc., preferably phenoxy resins. (G) Components may be used alone or in combination of two or more.
[0141] The weight average molecular weight of the (G) thermoplastic resin in terms of polystyrene is preferably 2,000 or more, more preferably 5,000 or more, and even more preferably 10,000 or more. The upper limit is preferably 100,000 or less, more preferably 70,000 or less, and even more preferably 50,000 or less.
[0142] The weight average molecular weight of the component (G) in terms of polystyrene can be measured by gel permeation chromatography (GPC). Specifically, the weight average molecular weight of the component (G) in terms of polystyrene can be calculated as follows: as a measuring device, LC-9A / RID-6A manufactured by Shimadzu Corporation is used; as a column, Shodex K-800P / K-804L / K-804L manufactured by Showa Denko K.K. is used; as a mobile phase, chloroform or the like is used, and the measurement is performed at a column temperature of 40°C, and the calculation is performed using a standard curve of standard polystyrene.
[0143] As phenoxy resin, for example, phenoxy resin having one or more skeletons selected from bisphenol A skeleton, bisphenol F skeleton, bisphenol S skeleton, bisphenol acetophenone skeleton, novolac skeleton, biphenyl skeleton, fluorene skeleton, dicyclopentadiene skeleton, norbornene skeleton, naphthalene skeleton, anthracene skeleton, adamantane skeleton, terpene skeleton, and trimethylcyclohexane skeleton can be mentioned. The terminal of phenoxy resin can be any functional group such as phenolic hydroxyl group and epoxy group. Phenoxy resin can be used alone or in combination of two or more. Specific examples of phenoxy resins include "1256" and "4250" (both are phenoxy resins containing a bisphenol A skeleton), "YX8100" (a phenoxy resin containing a bisphenol S skeleton), and "YX6954" (a phenoxy resin containing a bisphenol acetophenone skeleton) manufactured by Mitsubishi Chemical Corporation. In addition, "FX280" and "FX293" manufactured by Nippon Steel Chemical Materials Co., Ltd., "YL7500BH30", "YX6954BH30", "YX7553", "YX7553BH30", "YL7769BH30", "YL6794", "YL7213", "YL7290" and "YL7482" manufactured by Mitsubishi Chemical Corporation can also be mentioned.
[0144] Examples of the polyvinyl acetal resin include polyvinyl formal resin and polyvinyl butyral resin, and polyvinyl butyral resin is preferred. Specific examples of the polyvinyl acetal resin include "Denka Butyral 4000-2", "Denka Butyral 5000-A", "Denka Butyral 6000-C", and "Denka Butyral 6000-EP" manufactured by Denki Kagaku Kogyo Co., Ltd., and S-LEC BH series, BX series (e.g., BX-5Z), KS series (e.g., KS-1), BL series, and BM series manufactured by Sekisui Chemical Co., Ltd.
[0145] Specific examples of polyimide resins include "RIKACOAT SN20" and "RIKACOAT PN20" manufactured by Shin Nippon Chemical Co., Ltd. Specific examples of polyimide resins include: linear polyimide obtained by reacting difunctional hydroxy-terminated polybutadiene, a diisocyanate compound and a tetrabasic acid anhydride (polyimide described in Japanese Patent Application Publication No. 2006-37083), polyimide containing a polysiloxane skeleton (polyimide described in Japanese Patent Application Publication No. 2002-12667 and Japanese Patent Application Publication No. 2000-319386, etc.), and other modified polyimides.
[0146] Specific examples of polyamide-imide resins include "VYLOMAX HR11NN" and "VYLOMAX HR16NN" manufactured by Toyobo Co., Ltd. Specific examples of polyamide-imide resins include modified polyamide-imides such as "KS9100" and "KS9300" (polyamide-imide containing a polysiloxane skeleton) manufactured by Hitachi Chemical Co., Ltd.
[0147] Specific examples of polyethersulfone resins include "PES5003P" manufactured by Sumitomo Chemical Co., Ltd., etc. Specific examples of polyphenylene ether resins include "OPE-2St 1200" manufactured by Mitsubishi Gas Chemical Co., Ltd., etc. Specific examples of polyetheretherketone resins include "SUMIPLOY K" manufactured by Sumitomo Chemical Co., Ltd., etc. Specific examples of polyetherimide resins include "ULTEM" manufactured by GE, etc.
[0148] Specific examples of the polysulfone resin include polysulfone "P1700" and "P3500" manufactured by Solvay Advanced Polymers.
[0149] Examples of the polyolefin resin include ethylene-based copolymer resins such as low-density polyethylene, ultra-low-density polyethylene, high-density polyethylene, ethylene-vinyl acetate copolymers, ethylene-ethyl acrylate copolymers, and ethylene-methyl acrylate copolymers.
[0150] Examples of the polyester resin include polyethylene terephthalate resin, polyethylene naphthalate resin, polybutylene terephthalate resin, polybutylene naphthalate resin, polytrimethylene terephthalate resin, polytrimethylene naphthalate resin, and polycyclohexane dimethyl terephthalate resin.
[0151] When the resin composition contains (G) thermoplastic resin, its content is not particularly limited. When the non-volatile components other than (B) inorganic filler in the resin composition are set to 100% by mass, it is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, further preferably 0.5% by mass or more, and particularly preferably 1% by mass or more. The upper limit of the content of (G) thermoplastic resin is not particularly limited. When the non-volatile components other than (B) inorganic filler in the resin composition are set to 100% by mass, it is preferably 30% by mass or less, more preferably 10% by mass or less, further preferably 5% by mass or less, and particularly preferably 3% by mass or less.
[0152] <(H) Other additives>
[0153] The resin composition of the present invention may further contain any additive as a non-volatile component. Examples of such additives include organic metal compounds such as organic copper compounds, organic zinc compounds, and organic cobalt compounds; colorants such as phthalocyanine blue, phthalocyanine green, iodine green, diazo yellow, crystal violet, titanium oxide, and carbon black; polymerization inhibitors such as hydroquinone, catechol, pyrogallol, and phenothiazine; leveling agents such as siloxane; thickeners such as bentonite and montmorillonite; defoamers such as silicone defoamers, acrylic defoamers, fluorine defoamers, and vinyl resin defoamers; ultraviolet light absorbers such as benzotriazole ultraviolet light absorbers; adhesion enhancers such as urea silane; adhesion imparting agents such as silane coupling agents, triazole adhesion imparting agents, tetrazole adhesion imparting agents, and triazine adhesion imparting agents; antioxidants such as hindered phenol antioxidants and hindered amine antioxidants; fluorescent whitening agents such as stilbene derivatives; surfactants such as fluorine surfactants and silicone surfactants, and the like. The additives may be used alone or in combination of two or more at any ratio. (H) The content of other additives may be appropriately set by those skilled in the art.
[0154] <(I) Organic solvent>
[0155] For the resin composition of the present invention, in addition to the above-mentioned non-volatile components, as a volatile component, it sometimes contains any organic solvent. As (I) organic solvent, a known organic solvent can be used appropriately, and its type is not particularly limited. As (I) organic solvent, for example: ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, etc.; ester solvents such as methyl acetate, ethyl acetate, butyl acetate, isobutyl acetate, isoamyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, etc.; ether solvents such as tetrahydropyran, tetrahydrofuran, 1,4-dioxane, diethyl ether, diisopropyl ether, dibutyl ether, diphenyl ether, etc.; alcohol solvents such as methanol, ethanol, propanol, butanol, ethylene glycol, etc.; 2-ethoxyethyl acetate, propylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, carbitol acetate (ethyl diglycol Ether ester solvents such as acetate), γ-butyrolactone, methoxypropionic acid methyl ester; ester alcohol solvents such as methyl lactate, ethyl lactate, 2-hydroxyisobutyric acid methyl ester; ether alcohol solvents such as 2-methoxypropanol, 2-methoxyethanol, 2-ethoxyethanol, propylene glycol monomethyl ether, diethylene glycol monobutyl ether (butyl carbitol); amide solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone; sulfoxide solvents such as dimethyl sulfoxide; nitrile solvents such as acetonitrile and propionitrile; aliphatic hydrocarbon solvents such as hexane, cyclopentane, cyclohexane, methylcyclohexane; aromatic hydrocarbon solvents such as benzene, toluene, xylene, ethylbenzene, trimethylbenzene, etc. (I) The organic solvent can be used alone or in combination of two or more in any ratio. (I) The content of the organic solvent can be appropriately set by those skilled in the art.
[0156] <Method for producing resin composition>
[0157] The resin composition of the present invention can be manufactured in the following manner, for example: in any reaction vessel, in any order and / or partly or entirely, simultaneously add (A) epoxy resin, (B) inorganic filler, (C) granular or non-granular elastomer, (D) curing agent used as required, (E) curing accelerator used as required, (F) flame retardant used as required, (G) thermoplastic resin used as required, (H) other additives used as required, and (I) organic solvent used as required, and mix. In addition, in the process of adding each component and mixing, the temperature can be appropriately set, and heating and / or cooling can be performed temporarily or throughout. In addition, in the process of adding each component and mixing, stirring or vibration can be performed. In addition, when adding and mixing or afterwards, for example, stirring devices such as mixers can be used to stir the resin composition so that it is evenly dispersed.
[0158] <Characteristics of resin composition>
[0159] The resin composition of the present invention comprises (A) an epoxy resin, (B) an inorganic filler, and (C) a granular or non-granular elastomer, and the specific surface area of the component (B) is 10 m 2 / g or more, the content of component (C) is 35% by mass or less (the component ratio excluding component (B)), and the average particle size of component (C) is 0.8 μm or less. Therefore, warping of the cured product can be suppressed, and excellent insulation reliability, adhesion, and small-diameter through-hole formation can be achieved.
[0160] For the resin composition of the present invention, from the perspective of suppressing the warping of the cured product, for example, when a resin composition layer with a thickness of 15 μm and 14 cm square, which is pressed onto one side of a glass cloth-based epoxy resin copper-clad laminate (the copper foil has a thickness of 3 μm and the substrate has a thickness of 0.15 mm), is cured at 190°C for 90 minutes, the warping can be preferably less than 3 cm, more preferably less than 2 cm, and particularly preferably less than 1 cm.
[0161] The cured product of the resin composition of the present invention may preferably have a resistance value of 1.0×10 10 Ω or more, more preferably 1.0×10 7 Ω or more, more preferably 1.0×10 6 Ω or more, particularly preferably 1.0×10 5 Ω or more.
[0162] For the cured product of the resin composition of the present invention, from the perspective of excellent adhesion, the resin composition layer that is crimped on the roughened surface of the copper foil (Ra value = 1 μm) at 100°C and 0.74 MPa for 30 seconds is cured at 190°C for 90 minutes to form a cured product layer, and then the copper foil is peeled off 35 mm from the cured product layer in the vertical direction at a speed of 50 mm / min. At this time, the peel strength (copper foil peel strength before HAST) can be preferably 0.50 kgf / cm or more, more preferably 0.55 kgf / cm or more, further preferably 0.60 kgf / cm or more, and particularly preferably 0.65 kgf / cm or more.
[0163] In addition, a resin composition layer that was crimped on a roughened surface of a copper foil (Ra value = 1 μm) at 100°C and 0.74 MPa for 30 seconds was cured at 190°C for 90 minutes to form a cured layer, and then subjected to conditions of 130°C, 85% relative humidity, and a DC voltage of 3.3 V for 200 hours. Then, the copper foil was peeled off 35 mm from the cured layer in a vertical direction at a speed of 50 mm / min. The peel strength (copper foil peel strength after HAST) at this time may preferably be 0.20 kgf / cm or more, more preferably 0.30 kgf / cm or more, further preferably 0.35 kgf / cm or more, and particularly preferably 0.40 kgf / cm or more.
[0164] In addition, under the conditions of the following Test Example 4, the cured layer obtained by curing the resin composition of the present invention at 130°C for 30 minutes and 170°C for 30 minutes was roughened, and a conductor layer with a thickness of 20 μm was formed by a semi-additive method. Then, the conductor layer was peeled off from the cured layer in a vertical direction for 35 mm at a speed of 50 mm / min. At this time, the peel strength (plating peel strength) can be preferably 0.20 kgf / cm or more, more preferably 0.30 kgf / cm or more, further preferably 0.40 kgf / cm or more, and particularly preferably 0.45 kgf / cm or more.
[0165] For the cured product of the resin composition of the present invention, from the aspect of excellent small-diameter through-hole formation, the ratio of the bottom area to the top area of the through-hole formed in the roughened layer under the conditions of the following Test Example 5 may be preferably 50% or more, particularly preferably 60% or more. The upper limit of the ratio of the bottom area to the top area is not particularly limited, and may be, for example, 100%, 98%, 95%, 90%, etc.
[0166] <Application of resin composition>
[0167] The resin composition of the present invention can be suitably used as a resin composition for insulating purposes, especially a resin composition for forming an insulating layer. Specifically, it can be suitably used as: a resin composition for forming "the insulating layer for forming a conductor layer (the conductor layer is formed on the insulating layer, and the conductor layer includes a rewiring layer)" (a resin composition for forming an insulating layer for forming a conductor layer). In addition, in the printed wiring board described later, it can be suitably used as: a resin composition for forming an insulating layer of a printed wiring board (a resin composition for forming an insulating layer of a printed wiring board). The resin composition of the present invention can also be widely used in sheet-like laminated materials such as resin sheets, prepregs, solder resists, bottom filling materials, chip bonding materials, semiconductor sealing materials, filling resins, component embedding resins, etc. that require resin compositions.
[0168] In addition, for example, when a semiconductor chip package is manufactured through the following steps (1) to (6), the resin composition of the present invention can also be suitably used as a resin composition for a rewiring forming layer (resin composition for forming a rewiring forming layer) as an insulating layer for forming a rewiring layer, and a resin composition for sealing a semiconductor chip (resin composition for sealing a semiconductor chip). When manufacturing a semiconductor chip package, a rewiring layer may be further formed on the sealing layer;
[0169] (1) a step of laminating a temporary fixing film on a substrate,
[0170] (2) a step of temporarily fixing the semiconductor chip on a temporary fixing film,
[0171] (3) a step of forming a sealing layer on a semiconductor chip,
[0172] (4) a step of peeling the substrate and the temporary fixing film from the semiconductor chip,
[0173] (5) forming a rewiring formation layer as an insulating layer on the surface of the semiconductor chip from which the substrate and the temporary fixing film have been peeled off, and
[0174] (6) A step of forming a rewiring layer as a conductive layer on the rewiring formation layer.
[0175] Furthermore, the resin composition of the present invention forms an insulating layer having good component embedding properties, and therefore can be suitably used also when the printed wiring board is a component-embedded wiring board.
[0176] <Sheet-shaped laminated materials>
[0177] The resin composition of the present invention may be used by coating in a varnish state, but is usually preferably used in the form of a sheet-like laminate containing the resin composition in industrial terms.
[0178] As the sheet-like laminated material, the following resin sheets and prepregs are preferred.
[0179] In one embodiment, the resin sheet includes a support and a resin composition layer provided on the support, and the resin composition layer is formed of the resin composition of the present invention.
[0180] From the viewpoint of thinning the printed wiring board and providing a cured product with excellent insulation even if the cured product of the resin composition is a thin film, the thickness of the resin composition layer is preferably 50 μm or less, more preferably 40 μm or less. The lower limit of the thickness of the resin composition layer is not particularly limited, and can usually be 5 μm or more, 10 μm or more, etc.
[0181] Examples of the support include films made of plastic materials, metal foils, and release papers, and films made of plastic materials and metal foils are preferred.
[0182] When a film formed of a plastic material is used as a support, examples of the plastic material include polyesters such as polyethylene terephthalate (hereinafter sometimes referred to as "PET") and polyethylene naphthalate (hereinafter sometimes referred to as "PEN"), polycarbonate (hereinafter sometimes referred to as "PC"), acrylic polymers such as polymethyl methacrylate (PMMA), cyclic polyolefins, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, polyimide, etc. Among them, polyethylene terephthalate and polyethylene naphthalate are preferred, and inexpensive polyethylene terephthalate is particularly preferred.
[0183] When a metal foil is used as a support, examples of the metal foil include copper foil and aluminum foil, preferably copper foil. The copper foil may be a foil made of a single metal of copper or an alloy of copper and other metals (e.g., tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.).
[0184] The surface of the support to be in contact with the resin composition layer may be subjected to matte treatment, corona treatment, or antistatic treatment.
[0185] In addition, as a support, a support with a release layer having a release layer on the surface bonded to the resin composition layer can be used. As a release agent used in the release layer of a support with a release layer, for example, one or more release agents selected from alkyd resins, polyolefin resins, polyurethane resins, and silicone resins can be cited. The support with a release layer can use a commercial product, for example, as a PET film with a release layer with an alkyd resin-based release agent as the main component, "SK-1", "AL-5", "AL-7" made by Lindeco, "Lumirror T60" made by Toray, "Purex" made by Teijin, "Unipeel" made by UNITIKA, etc.
[0186] The thickness of the support is not particularly limited, but is preferably in the range of 5 μm to 75 μm, and more preferably in the range of 10 μm to 60 μm. When a support with a release layer is used, the thickness of the entire support with a release layer is preferably in the above range.
[0187] In one embodiment, the resin sheet may further include an arbitrary layer as required. As the arbitrary layer, for example, a protective film selected according to the support provided on the surface of the resin composition layer that is not bonded to the support (i.e., the surface on the opposite side of the support) can be cited. The thickness of the protective film is not particularly limited, for example, 1 μm to 40 μm. By laminating the protective film, dust and the like can be prevented from adhering to the surface of the resin composition layer or from being damaged on the surface of the resin composition layer.
[0188] The resin sheet can be produced, for example, by directly applying a liquid resin composition onto a support using a die coater or the like, or by preparing a resin varnish by dissolving the resin composition in an organic solvent and applying the varnish onto a support using a die coater or the like, and then drying the varnish to form a resin composition layer.
[0189] Examples of the organic solvent include the same organic solvents as those described as components of the resin composition. The organic solvent may be used alone or in combination of two or more.
[0190] Drying can be carried out by known methods such as heating and blowing hot air. There is no particular limitation on the drying conditions, and the drying is carried out in such a manner that the content of the organic solvent in the resin composition layer is 10% by mass or less, preferably 5% by mass or less. Although it varies with the boiling point of the organic solvent in the resin composition or resin varnish, for example, when a resin composition or resin varnish containing 30% to 60% by mass of an organic solvent is used, the resin composition layer can be formed by drying at 50°C to 150°C for 3 minutes to 10 minutes.
[0191] The resin sheet can be stored by winding it into a roll. When the resin sheet has a protective film, it can be used by peeling off the protective film.
[0192] In one embodiment, the prepreg is formed by impregnating the resin composition of the present invention into a sheet-like fiber base material.
[0193] The sheet-like fiber substrate used in the prepreg is not particularly limited, and glass cloth, aramid nonwoven fabric, liquid crystal polymer nonwoven fabric, etc. can be used as a sheet-like fiber substrate commonly used as a prepreg substrate. From the viewpoint of thinning the printed wiring board, the thickness of the sheet-like fiber substrate is preferably 50 μm or less, more preferably 40 μm or less, further preferably 30 μm or less, and particularly preferably 20 μm or less. The lower limit of the thickness of the sheet-like fiber substrate is not particularly limited. It is usually 10 μm or more.
[0194] The prepreg can be produced by a known method such as a hot melt method or a solvent method.
[0195] The thickness of the prepreg may be in the same range as that of the resin composition layer in the above-mentioned resin sheet.
[0196] The sheet-like laminated material of the present invention can be suitably used to form an insulating layer of a printed wiring board (for an insulating layer of a printed wiring board), and can be more suitably used to form an interlayer insulating layer of a printed wiring board (for an interlayer insulating layer of a printed wiring board).
[0197] <Printed wiring board>
[0198] The printed wiring board of the present invention includes an insulating layer formed of a cured product obtained by curing the resin composition of the present invention.
[0199] The printed wiring board can be produced, for example, by using the above-mentioned resin sheet and by a method including the following steps (I) and (II).
[0200] (I) a step of laminating a resin sheet on the inner substrate so that the resin composition layer of the resin sheet is bonded to the inner substrate,
[0201] (II) A step of curing (for example, thermally curing) the resin composition layer to form an insulating layer.
[0202] The "inner substrate" used in step (I) refers to a member that becomes a substrate of a printed wiring board, and examples thereof include a glass epoxy substrate, a metal substrate, a polyester substrate, a polyimide substrate, a BT resin substrate, a thermosetting polyphenylene ether substrate, and the like. In addition, the substrate may have a conductor layer on one or both sides thereof, and the conductor layer may be patterned. An inner substrate having a conductor layer (circuit) formed on one or both sides of a substrate is sometimes referred to as an "inner circuit substrate". In addition, when manufacturing a printed wiring board, an intermediate product to be further formed with an insulating layer and / or a conductor layer is also included in the "inner substrate" referred to in the present invention. When the printed wiring board is a circuit board with built-in components, an inner substrate with built-in components can be used.
[0203] The lamination of the inner substrate and the resin sheet can be performed, for example, by heat-pressing the resin sheet to the inner substrate from the support body side. As a component for heat-pressing the resin sheet to the inner substrate (hereinafter also referred to as a "heat-pressing component"), for example, a heated metal plate (SUS end plate, etc.) or a metal roller (SUS roller) can be cited. It should be noted that it is preferred that the heat-pressing component is not directly pressed against the resin sheet, but is pressed through an elastic material such as heat-resistant rubber so that the resin sheet fully follows the surface unevenness of the inner substrate.
[0204] The lamination of the inner substrate and the resin sheet can be implemented by vacuum lamination. In the vacuum lamination method, the heating and pressing temperature is preferably 60°C to 160°C, more preferably in the range of 80°C to 140°C, the heating and pressing pressure is preferably 0.098MPa to 1.77MPa, more preferably in the range of 0.29MPa to 1.47MPa, and the heating and pressing time is preferably 20 seconds to 400 seconds, more preferably in the range of 30 seconds to 300 seconds. The lamination can preferably be implemented under reduced pressure conditions of 26.7hPa or less.
[0205] Lamination can be performed using a commercially available vacuum laminator. Examples of commercially available vacuum laminators include a vacuum pressure laminator manufactured by Meiki Mfg. Co., Ltd., a vacuum applicator manufactured by Nikko-Materials Co., Ltd., and a batch vacuum pressure laminator.
[0206] After lamination, at normal pressure (atmospheric pressure), for example, the heating and pressing member is pressed from the support body side, thereby, the laminated resin sheet can be smoothed. The pressing conditions for the smoothing treatment can be set to the same conditions as the heating and pressing conditions for the above-mentioned lamination. The smoothing treatment can be performed using a commercially available laminator. It should be noted that the lamination and smoothing treatment can be performed continuously using the above-mentioned commercially available vacuum laminator.
[0207] The support may be removed between step (I) and step (II), or may be removed after step (II).
[0208] In step (II), the resin composition layer is cured (eg, thermally cured) to form an insulating layer composed of a cured product of the resin composition. The curing conditions of the resin composition layer are not particularly limited, and conditions commonly used in forming an insulating layer of a printed wiring board can be used.
[0209] For example, the heat curing conditions of the resin composition layer vary depending on the type of the resin composition, and the curing temperature is preferably 120° C. to 240° C., more preferably 150° C. to 220° C., and further preferably 170° C. to 210° C. The curing time is preferably 5 minutes to 120 minutes, more preferably 10 minutes to 100 minutes, and further preferably 15 minutes to 100 minutes.
[0210] The resin composition layer may be preheated at a temperature lower than the curing temperature before the resin composition layer is thermally cured. For example, the resin composition layer may be preheated at a temperature of 50° C. to 120° C., preferably 60° C. to 115° C., more preferably 70° C. to 110° C., for 5 minutes or more, preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes, and further preferably 15 minutes to 100 minutes before the resin composition layer is thermally cured.
[0211] When manufacturing a printed wiring board, the step of (III) opening a hole in the insulating layer, the step of (IV) roughening the insulating layer, and the step of (V) forming a conductor layer can be further implemented. These steps (III) to (V) can be implemented according to various methods known to those skilled in the art that can be used in the manufacture of a printed wiring board. It should be noted that when the support body is removed after step (II), the removal of the support body can be implemented between step (II) and step (III), between step (III) and step (IV), or between step (IV) and step (V). In addition, as needed, the formation of the insulating layer and the conductor layer of steps (II) to (V) can also be repeatedly implemented to form a multilayer wiring board.
[0212] In another embodiment, the printed wiring board of the present invention can be produced using the above-mentioned prepreg. The production method is basically the same as that in the case of using a resin sheet.
[0213] Step (III) is a step of drilling holes in the insulating layer, thereby forming holes such as through holes and through holes in the insulating layer. Step (III) can be implemented using, for example, a drill, laser, plasma, etc., depending on the composition of the resin composition used in forming the insulating layer. The size or shape of the hole can be appropriately determined according to the design of the printed wiring board.
[0214] Step (IV) is a step of roughening the insulating layer. Usually, in step (IV), smear removal is also performed. The steps and conditions of the roughening treatment are not particularly limited, and the known steps and conditions commonly used when forming the insulating layer of the printed wiring board can be adopted. For example, the insulating layer can be roughened by sequentially performing swelling treatment using a swelling solution, roughening treatment using an oxidant, and neutralization treatment using a neutralizing solution.
[0215] There are no particular restrictions on the swelling liquid used in the roughening treatment, and examples include alkaline solutions, surfactant solutions, etc., preferably alkaline solutions, and more preferably sodium hydroxide solutions and potassium hydroxide solutions. Commercially available swelling liquids include, for example, "Swelling Dip Securiganth P" and "Swelling Dip Securiganth SBU" manufactured by Atotech Japan. There are no particular restrictions on the swelling treatment using the swelling liquid, and for example, it can be carried out by immersing the insulating layer in a swelling liquid at 30°C to 90°C for 1 minute to 20 minutes. From the viewpoint of suppressing the swelling of the resin of the insulating layer to an appropriate level, it is preferred to immerse the insulating layer in a swelling liquid at 40°C to 80°C for 5 minutes to 15 minutes.
[0216] As the oxidant used in the roughening treatment, there is no particular limitation, and an alkaline permanganate solution formed by dissolving potassium permanganate or sodium permanganate in an aqueous solution of sodium hydroxide can be cited. The roughening treatment using an oxidant such as an alkaline permanganate solution is preferably carried out by immersing the insulating layer in an oxidant solution heated to 60°C to 100°C for 10 minutes to 30 minutes. In addition, the concentration of permanganate in the alkaline permanganate solution is preferably 5% to 10% by mass. As commercially available oxidants, alkaline permanganate solutions such as "Concentrate Compact CP" and "Dosing Solution Securiganth P" manufactured by Atotech Japan can be cited.
[0217] The neutralizing solution used in the roughening treatment is preferably an acidic aqueous solution, and examples of commercially available products include "Reduction Solution Securiganth P" manufactured by Atotech Japan Co., Ltd.
[0218] The treatment with the neutralizing solution can be performed by immersing the treated surface after the roughening treatment with the oxidizing agent in the neutralizing solution at 30° C. to 80° C. for 5 to 30 minutes. In view of operability, etc., it is preferred to immerse the object after the roughening treatment with the oxidizing agent in the neutralizing solution at 40° C. to 70° C. for 5 to 20 minutes.
[0219] In one embodiment, the arithmetic mean roughness (Ra) of the insulating layer surface after roughening treatment is not particularly limited, preferably less than 500nm, more preferably less than 400nm, and more preferably less than 300nm. There is no particular restriction on the lower limit, for example, it can be more than 1nm, more than 2nm, etc. In addition, the root mean square roughness (Rq) of the insulating layer surface after roughening treatment is preferably less than 500nm, more preferably less than 400nm, and more preferably less than 300nm. There is no particular restriction on the lower limit, for example, it can be more than 1nm, more than 2nm, etc. The arithmetic mean roughness (Ra) and root mean square roughness (Rq) of the insulating layer surface can be measured using a non-contact surface roughness meter.
[0220] Step (V) is a step of forming a conductor layer, and a conductor layer is formed on the insulating layer. The conductor material used in the conductor layer is not particularly limited. In a preferred embodiment, the conductor layer comprises one or more metals selected from gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin and indium. The conductor layer can be a single metal layer or an alloy layer. As the alloy layer, for example, a layer formed by an alloy of two or more metals selected from the above metals (for example, nickel-chromium alloy, copper-nickel alloy and copper-titanium alloy) can be cited. Among them, from the viewpoint of versatility, cost, ease of patterning, etc. of the formation of the conductor layer, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver or copper, or an alloy layer of nickel-chromium alloy, copper-nickel alloy, or copper-titanium alloy is preferred, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver or copper, or an alloy layer of nickel-chromium alloy is more preferred, and a single metal layer of copper is further preferred.
[0221] The conductor layer may be a single-layer structure, or a multilayer structure in which two or more single metal layers or alloy layers formed of different types of metals or alloys are stacked. When the conductor layer is a multilayer structure, the layer in contact with the insulating layer is preferably a single metal layer of chromium, zinc or titanium, or an alloy layer of nickel-chromium alloy.
[0222] The thickness of the conductor layer depends on the desired design of the printed wiring board, but is usually 3 μm to 35 μm, preferably 5 μm to 30 μm.
[0223] In one embodiment, the conductor layer can be formed by plating. For example, the surface of the insulating layer can be plated using a conventionally known technique such as a semi-additive method or a full-additive method to form a conductor layer having a desired wiring pattern. From the perspective of manufacturing simplicity, it is preferably formed using a semi-additive method. An example of forming a conductor layer using a semi-additive method is shown below.
[0224] First, a plating seed layer is formed on the surface of the insulating layer by electroless plating. Next, a mask pattern is formed on the formed plating seed layer to expose a portion of the plating seed layer corresponding to the desired wiring pattern. A metal layer is formed on the exposed plating seed layer by electrolytic plating, and then the mask pattern is removed. Then, the unnecessary plating seed layer is removed by etching or the like, and a conductor layer having a desired wiring pattern can be formed.
[0225] In other embodiments, the conductor layer can be formed using a metal foil. When a metal foil is used to form a conductor layer, step (V) is preferably implemented between step (I) and step (II). For example, after step (I), the support is removed and a metal foil is laminated on the surface of the exposed resin composition layer. The lamination of the resin composition layer and the metal foil can be implemented using a vacuum lamination method. The lamination conditions can be the same as those described for step (I). Next, step (II) is implemented to form an insulating layer. Then, using the metal foil on the insulating layer, a conductor layer with a desired wiring pattern can be formed using previously known techniques such as a subtractive method and an improved semi-additive method.
[0226] The metal foil can be produced by a known method such as electrolysis or rolling. Commercially available metal foils include HLP foil and JXUT-III foil manufactured by JX Nippon Mining & Metals Co., Ltd., and 3EC-III foil and TP-III foil manufactured by Mitsui Mining & Co., Ltd.
[0227] <Semiconductor devices>
[0228] The semiconductor device of the present invention includes the printed wiring board of the present invention. The semiconductor device of the present invention can be produced using the printed wiring board of the present invention.
[0229] Examples of the semiconductor device include various semiconductor devices used in electrical products (eg, computers, mobile phones, digital cameras, and televisions) and vehicles (eg, motorcycles, cars, trains, ships, and airplanes).
[0230] Example
[0231] The present invention is specifically described below by way of examples. The present invention is not limited to these examples. It should be noted that, hereinafter, unless otherwise clearly stated, "parts" and "%" indicating amounts represent "parts by mass" and "% by mass", respectively.
[0232] <Measurement of average particle size of inorganic filler>
[0233] 100 mg of inorganic filler, 0.1 g of dispersant ("SN9228" manufactured by Sannopco) and 10 g of methyl ethyl ketone were weighed into a vial and dispersed by ultrasonic wave for 20 minutes. The particle size distribution was measured by batch cell method using laser diffraction particle size distribution measuring device ("SALD-2200" manufactured by Shimadzu Corporation) to calculate the average particle size based on the median particle size.
[0234] <Measurement of average particle size of rubber particles>
[0235] The average particle size of the rubber particles can be measured using a dynamic light scattering method. Specifically, the rubber particles are uniformly dispersed in an appropriate organic solvent using an ultrasonic method or the like, and a particle size distribution of the rubber particles is prepared based on mass using a concentrated particle size analyzer ("FPAR-1000" manufactured by Otsuka Electronics Co., Ltd.), and the median particle size is measured as the average particle size.
[0236] <Synthesis example 1>
[0237] In a reaction vessel, 69 g of difunctional hydroxy-terminated polybutadiene (G-1000, manufactured by Nippon Soda Co., Ltd., number average molecular weight = 1,000, hydroxyl equivalent = 1,800 g / eq.), 40 g of Ipsol 150 (aromatic hydrocarbon mixed solvent: manufactured by Idemitsu Petrochemical Co., Ltd.), and 0.005 g of dibutyltin laurate were mixed and uniformly dissolved. After becoming uniform, the temperature was raised to 50° C., and 8 g of isophorone diisocyanate (manufactured by Evonik Degussa Japan Co., Ltd., IPDI, isocyanate group equivalent = 113 g / eq.) was further added while stirring, and the reaction was carried out for about 3 hours. Next, after the reaction product was cooled to room temperature, 23 g of cresol novolac resin (KA-1160, manufactured by DIC Corporation, hydroxyl equivalent = 117 g / eq.) and 60 g of ethyl diglycol acetate (diethylene glycol monoethyl ether acetate) (manufactured by Daicel Corporation) were added thereto, and the temperature was raised to 80°C while stirring, and the reaction was carried out for about 4 hours. The FT-IR at 2250 cm -1 The disappearance of the NCO peak was confirmed. The disappearance of the NCO peak was considered as the end point of the reaction. The reactants were cooled to room temperature and filtered with a 100-mesh filter cloth to obtain a liquid polybutadiene resin containing phenolic hydroxyl groups (non-volatile components of 50% by mass). The number average molecular weight was 4,500.
[0238] <Synthesis example 2>
[0239] In a reaction vessel, 69 g of a difunctional hydroxy-terminated polybutadiene (G-2000, manufactured by Nippon Soda Co., Ltd., number average molecular weight = 3,000, hydroxyl equivalent = 1,800 g / eq.), 40 g of Ipsol 150 (aromatic hydrocarbon mixed solvent: manufactured by Idemitsu Petrochemical Co., Ltd.), and 0.005 g of dibutyltin laurate were mixed and uniformly dissolved. After becoming uniform, the temperature was raised to 50° C., and 8 g of isophorone diisocyanate (manufactured by Evonik Degussa Japan Co., Ltd., IPDI, isocyanate equivalent = 113 g / eq.) was further added with stirring, and the reaction was carried out for about 3 hours. Next, after the reaction product was cooled to room temperature, 23 g of a cresol novolac resin (KA-1160, manufactured by DIC Corporation, hydroxyl equivalent = 117 g / eq.) and 60 g of carbitol acetate (manufactured by Daicel Corporation) were added thereto, and the temperature was raised to 80° C. with stirring, and the reaction was carried out for about 4 hours. By FT-IR at 2250cm -1 The disappearance of the NCO peak was confirmed. The disappearance of the NCO peak was considered as the end point of the reaction. The reactant was cooled to room temperature and filtered with a 100-mesh filter cloth to obtain a liquid polybutadiene resin containing phenolic hydroxyl groups (non-volatile components of 50% by mass). The number average molecular weight was 5,500.
[0240] <Example 1>
[0241] While stirring, 10 parts of bisphenol A epoxy resin ("828US" manufactured by Mitsubishi Chemical Corporation, epoxy equivalent of about 180 g / eq.), 10 parts of naphthalene epoxy resin ("HP-4032SS" manufactured by DIC Corporation, epoxy equivalent of about 140 g / eq.), 20 parts of biphenyl epoxy resin ("NC3000L" manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent of about 269 g / eq.), and 20 parts of biphenyl epoxy resin ("YX4000H" manufactured by Mitsubishi Chemical Corporation, epoxy equivalent of about 190 g / eq.) were added. g / eq.), 20 parts of phosphazene resin ("PX-200" manufactured by Otsuka Chemical Co., Ltd.), 3 parts of phenoxy resin ("YX7553BH30" manufactured by Mitsubishi Chemical Corporation, a 1:1 solution of MEK and cyclohexanone with a solid content of 30% by mass), and 28 parts of polyurethane rubber particles ("MM-101SM" manufactured by Negami Industries, Ltd., an average particle size of 0.07 to 0.10 μm, a 4:1 solution of MEK and cyclohexane with a solid content of 30% by mass) were dissolved in 60 parts of MEK by heating.
[0242] After cooling to room temperature, 70 parts of an active ester curing agent ("HPC-8000-65T" manufactured by DIC Corporation, an active group equivalent of about 223 g / eq., a toluene solution with a solid content of 65% by mass), 6 parts of a phenol curing agent ("LA-3018-50P" manufactured by DIC Corporation, an active group equivalent of about 151 g / eq., a 2-methoxypropanol solution with a solid content of 50%), and 6 parts of a carbodiimide curing agent ("V- 03", active group equivalent of about 216 g / eq., toluene solution with a solid content of 50% by mass) 18 parts, a curing accelerator (4-dimethylaminopyridine (DMAP), a MEK solution with a solid content of 5% by mass) 6 parts, spherical silica ("UFP-20" manufactured by DENKA, with a specific surface area of 22 m2) surface-treated with N-phenyl-8-aminooctyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., molecular weight 325.2) 2 / g, average particle size: 0.15 μm) was uniformly dispersed using a high-speed rotary mixer, and then filtered using a cartridge filter ("SHP020" manufactured by ROKITECHNO) to prepare a resin composition.
[0243] <Example 2>
[0244] A resin composition was prepared in the same manner as in Example 1 except that 28 parts of polyurethane rubber particles (MM-101SM manufactured by Negami Industries, Ltd., with an average particle size of 0.07 to 0.10 μm and a solid content of 30% by mass of a 4:1 solution of MEK and cyclohexane) were replaced with 8.5 parts of a liquid polybutadiene resin containing an epoxy group (JP-100 manufactured by Nippon Soda Co., Ltd., with an epoxy equivalent of approximately 210 g / eq.).
[0245] <Example 3>
[0246] Spherical silica ("UFP-20" manufactured by DENKA Corporation, with a specific surface area of 22 m2) surface-treated with N-phenyl-8-aminooctyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., with a molecular weight of 325.2) was prepared. 2 / g, average particle size of 0.15 μm) was changed from 300 parts to 110 parts, and a resin composition was prepared in the same manner as in Example 1.
[0247] <Example 4>
[0248] A resin composition was prepared in the same manner as in Example 1 except that 28 parts of polyurethane rubber particles ("MM-101SM" manufactured by Negami Industries, with an average particle size of 0.07 to 0.10 μm and a solid content of 30% by mass of a 4:1 solution of MEK and cyclohexane) were replaced with 17 parts of a liquid polybutadiene resin containing phenolic hydroxyl groups obtained in Synthesis Example 1 (solid content of 50%, number average molecular weight: 4,500).
[0249] <Example 5>
[0250] A resin composition was prepared in the same manner as in Example 1 except that 28 parts of polyurethane rubber particles ("MM-101SM" manufactured by Negami Industries, with an average particle size of 0.07 to 0.10 μm and a solid content of 30% by mass of a 4:1 solution of MEK and cyclohexane) were replaced with 17 parts of a liquid polybutadiene resin containing phenolic hydroxyl groups obtained in Synthesis Example 2 (solid content of 50%, number average molecular weight: 5,500).
[0251] <Example 6>
[0252] A resin composition was prepared in the same manner as in Example 1 except that 28 parts of polyurethane rubber particles ("MM-101SM" manufactured by Negami Industries, with an average particle size of 0.07 to 0.10 μm and a solid content of 30% by mass of a 4:1 solution of MEK and cyclohexane) were replaced with 80 parts of a liquid polybutadiene resin containing phenolic hydroxyl groups obtained in Synthesis Example 1 (solid content of 50%, number average molecular weight: 4,500).
[0253] <Example 7>
[0254] A resin composition was prepared in the same manner as in Example 1 except that 28 parts of polyurethane rubber particles (MM-101SM manufactured by Negami Industries, Ltd., a 4:1 solution of MEK and cyclohexane with an average particle size of 0.07 to 0.10 μm and a solid content of 30% by mass) were replaced with 8.5 parts of a liquid polybutadiene resin containing an epoxy group (JP-100 manufactured by Nippon Soda Co., Ltd., with an epoxy equivalent of approximately 210 g / eq.), and 70 parts of an active ester-based curing agent (HPC-8000-65T manufactured by DIC Corporation, an active group equivalent of approximately 223 g / eq., and a toluene solution with a solid content of 65% by mass) were replaced with 65 parts of an active ester-based curing agent (HPC-8150-60T manufactured by DIC Corporation, an active group equivalent of approximately 220 g / eq., and a toluene solution with a solid content of 60% by mass).
[0255] <Comparative Example 1>
[0256] 28 parts of polyurethane rubber particles ("MM-101SM" manufactured by Negami Industry Co., Ltd., average particle size of 0.07 to 0.10 μm, solid content of 30% by mass of a 4:1 solution of MEK and cyclohexane) were replaced with 28 parts of rubber particles ("MM-110SM" manufactured by Negami Industry Co., Ltd., average particle size of 1 μm, solid content of 30% by mass of a 4:1 solution of MEK and cyclohexanone), and spherical silica ("UFP-20" manufactured by DENKA Corporation, specific surface area of 22 m2) surface-treated with N-phenyl-8-aminooctyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., molecular weight of 325.2) was replaced with spherical silica ("UFP-20" manufactured by DENKA Corporation, specific surface area of 22 m2) surface-treated with N-phenyl-8-aminooctyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., molecular weight of 325. ... 2 / g, average particle size of 0.15 μm) was replaced with 300 parts of spherical silica (“SC2050-SXF” manufactured by Yaduma Co., Ltd., with a specific surface area of 5.9 m 2 / g, and an average particle size of 0.77 μm), a resin composition was prepared in the same manner as in Example 1.
[0257] <Comparative Example 2>
[0258] Spherical silica ("UFP-20" manufactured by DENKA Corporation, with a specific surface area of 22 m2) surface-treated with N-phenyl-8-aminooctyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., with a molecular weight of 325.2) was prepared. 2 / g, average particle size of 0.15 μm) was replaced with 300 parts of spherical silica (“SC2050-SXF” manufactured by Yaduma Co., Ltd., with a specific surface area of 5.9 m 2 / g, and an average particle size of 0.77 μm), a resin composition was prepared in the same manner as in Example 1.
[0259] <Comparative Example 3>
[0260] A resin composition was prepared in the same manner as in Example 1, except that 28 parts of polyurethane rubber particles ("MM-101SM" manufactured by Negami Industries, Ltd., with an average particle size of 0.07 to 0.10 μm and a solid content of 30% by mass of a 4:1 solution of MEK and cyclohexane) were replaced with 28 parts of rubber particles ("MM-110SM" manufactured by Negami Industries, Ltd., with an average particle size of 1 μm and a solid content of 30% by mass of a 4:1 solution of MEK and cyclohexanone).
[0261] <Comparative Example 4>
[0262] A resin composition was prepared in the same manner as in Example 1 except that 28 parts of polyurethane rubber particles (MM-101SM manufactured by Negami Industries, Ltd., average particle size 0.07 to 0.10 μm, 4:1 solution of MEK and cyclohexane with a solid content of 30% by mass) were not used.
[0263] <Comparative Example 5>
[0264] In Example 1, the resin composition was prepared in the same manner as in Example 1 except that 28 parts of polyurethane rubber particles ("MM-101SM" manufactured by Negami Industries, with an average particle size of 0.07 to 0.10 μm and a solid content of 30% by mass of a 4:1 solution of MEK and cyclohexane) were replaced with 160 parts of a liquid polybutadiene resin containing phenolic hydroxyl groups obtained in Synthesis Example 1 (solid content of 50%, number average molecular weight: 4,500).
[0265] <Production Example 1: Production of Resin Sheet A>
[0266] As a support, a PET film ("Lumirror R80" manufactured by Toray Industries, Ltd., 38 μm thick, 130° C. softening point, hereinafter sometimes referred to as "release PET") subjected to release treatment with an alkyd resin-based release agent ("AL-5" manufactured by Lintec) was prepared.
[0267] Each resin composition prepared in the embodiment or comparative example was uniformly coated on the release PET using a die coater so that the thickness of the resin composition layer after drying was 6 μm, and dried at 80°C for 1 minute, thereby obtaining a resin composition layer on the release PET. Next, the rough surface of a polypropylene film ("ALPHANMA-411" manufactured by Oji F-Tex Co., Ltd., with a thickness of 15 μm) as a protective film was laminated on the surface of the resin composition layer that was not bonded to the support so as to bond to the resin composition layer. Thus, a "resin sheet A" consisting of the release PET (support), the resin composition layer, and the protective film in this order was prepared.
[0268] <Production Example 2: Production of Resin Sheet B>
[0269] As a support, a PET film ("Lumirror R80" manufactured by Toray Industries, Ltd., 38 μm thick, 130° C. softening point, hereinafter sometimes referred to as "release PET") subjected to release treatment with an alkyd resin-based release agent ("AL-5" manufactured by Lintec) was prepared.
[0270] Each resin composition prepared in the embodiment or comparative example was uniformly coated on the release PET using a die coater so that the thickness of the resin composition layer after drying was 10 μm, and dried at 80°C for 2 minutes, thereby obtaining a resin composition layer on the release PET. Next, the rough surface of a polypropylene film ("ALPHANMA-411" manufactured by Oji F-Tex Co., Ltd., with a thickness of 15 μm) as a protective film was laminated on the surface of the resin composition layer that was not bonded to the support so as to bond to the resin composition layer. Thus, a "resin sheet B" consisting of the release PET (support), the resin composition layer, and the protective film in this order was prepared.
[0271] <Production Example 3: Production of Resin Sheet C>
[0272] As a support, a PET film ("Lumirror R80" manufactured by Toray Industries, Ltd., 38 μm thick, 130° C. softening point, hereinafter sometimes referred to as "release PET") subjected to release treatment with an alkyd resin-based release agent ("AL-5" manufactured by Lintec) was prepared.
[0273] Each resin composition prepared in the embodiment or comparative example was uniformly coated on the release PET using a die coater so that the thickness of the resin composition layer after drying was 15 μm, and dried at 80°C for 2 minutes, thereby obtaining a resin composition layer on the release PET. Next, the rough surface of a polypropylene film ("ALPHANMA-411" manufactured by Oji F-Tex Co., Ltd., with a thickness of 15 μm) as a protective film was laminated on the surface of the resin composition layer that was not bonded to the support so as to bond to the resin composition layer. Thus, a "resin sheet C" consisting of the release PET (support), the resin composition layer, and the protective film in this order was prepared.
[0274] <Test Example 1: Evaluation of insulation reliability>
[0275] (Fabrication of Evaluation Substrate)
[0276] (1) Base treatment of inner layer circuit board
[0277] As the inner layer circuit board, a glass cloth-based epoxy resin double-sided copper-clad laminate (copper foil thickness of 3 μm, substrate thickness of 0.15 mm, "HL832NSF LCA" manufactured by Mitsubishi Gas Chemical Co., Ltd., 255×340 mm in size) having circuit conductors (copper) formed in a wiring pattern of L / S (line width / line spacing) = 2 μm / 2 μm on both sides was prepared. For both sides of the inner layer circuit board, an organic coating (organic coating) treatment of the copper surface was performed using "FlatBOND-FT" manufactured by MEC Co., Ltd.
[0278] (2) Lamination of resin sheets
[0279] The protective film was peeled off from the resin sheet A prepared in Preparation Example 1, and laminated on both sides of the inner layer circuit substrate using an intermittent vacuum pressurization laminator (Nikko-Materials, 2-stage stacking laminator, CVP700) in a manner that the resin composition layer was in contact with the inner layer circuit substrate. Lamination was performed by the following method: decompression was performed for 30 seconds to make the air pressure below 13 hPa, and pressure bonding was performed at 130°C and a pressure of 0.74 MPa for 45 seconds. Next, hot pressing was performed at 120°C and a pressure of 0.5 MPa for 75 seconds.
[0280] (3) Thermal curing of resin composition layer
[0281] The inner layer circuit board laminated with the resin sheet was placed in an oven at 130°C for 30 minutes of heat curing, and then transferred to an oven at 170°C for 30 minutes of heat curing to form an insulating layer with a thickness of 5 μm, and the release PET was peeled off. This was referred to as "substrate A".
[0282] (4) Roughening process
[0283] A desmear process as a roughening process was performed on the insulating layer of the substrate A. In addition, as the desmear process, the following wet desmear process was performed.
[0284] Wet desmear treatment:
[0285] The substrate was immersed in a swelling solution ("Swelling Dip Securiganth P" manufactured by Atotech Japan, an aqueous solution of diethylene glycol monobutyl ether and sodium hydroxide) at 60°C for 5 minutes, then immersed in an oxidizing solution ("Concentrate Compact CP" manufactured by Atotech Japan, an aqueous solution of about 6% potassium permanganate and about 4% sodium hydroxide) at 80°C for 10 minutes, and finally immersed in a neutralizing solution ("Reduction Solution Securiganth P" manufactured by Atotech Japan, an aqueous solution of sulfuric acid) at 40°C for 5 minutes, and then dried at 80°C for 15 minutes. This was referred to as "roughened substrate A".
[0286] (5) Step of forming a conductor layer (5-1) Electroless plating step
[0287] In order to form a conductor layer on the surface of the insulating layer of the roughened substrate A, a plating step including the following steps 1 to 6 (copper plating step using a chemical solution manufactured by Atotech Japan Co., Ltd.) was performed to form a conductor layer.
[0288] 1. Alkali cleaning (cleaning and charge adjustment of the surface of the insulating layer with through holes)
[0289] The surface of the roughened substrate A was cleaned at 60° C. for 5 minutes using Cleaning Cleaner Securiganth 902 (trade name);
[0290] 2. Soft etching (cleaning inside through-holes)
[0291] For roughening the surface of substrate A, a sulfuric acid-acidified sodium persulfate aqueous solution was used for treatment at 30° C. for 1 minute;
[0292] 3. Pre-impregnation (for charge regulation of the surface of the Pd insulating layer)
[0293] For roughening the surface of substrate A, use Pre.Dip Neoganth B (trade name) at room temperature for 1 minute;
[0294] 4. Activator application (applying Pd to the surface of the insulating layer)
[0295] The surface of the roughened substrate A was treated with Activator Neoganth 834 (trade name) at 35° C. for 5 minutes;
[0296] 5. Reduction (reduction of Pd that has been given to the insulating layer)
[0297] The surface of the roughened substrate A was treated at 30° C. for 5 minutes using a mixture of Reducer Neoganth WA (trade name) and Reducer Acceralator 810 mod. (trade name);
[0298] 6. Electroless copper plating process (Cu is deposited on the surface of the insulating layer (Pd surface))
[0299] The surface of the roughened substrate A was treated at 35° C. for 20 minutes using a mixed solution of Basic Solution Printganth MSK-DK (trade name), Copper Solution Printganth MSK (trade name), Stabilizer Printganth MSK-DK (trade name), and Reducer Cu (trade name). The thickness of the formed electroless copper plating layer was 0.8 μm.
[0300] (5-2) Electrolytic plating process
[0301] Next, an electrolytic copper plating process was performed using a chemical solution made by Atotech Japan Co., Ltd. under the condition that the through hole was filled with copper. Then, as a resist pattern for patterning based on etching, a pad pattern with a diameter of 1 mm connected to the through hole and a circular conductor pattern with a diameter of 10 mm not connected to the lower conductor were used to form a conductor layer with a thickness of 10 μm on the surface of the insulating layer having a pad and a conductor pattern. Next, an annealing treatment was performed at 200°C for 90 minutes. This substrate was used as an "evaluation substrate".
[0302] (Measurement of insulation layer thickness)
[0303] The cross-section of the evaluation substrate was observed using a FIB-SEM composite device (SII NanoTechnology "SMI3050SE"). Specifically, a cross section perpendicular to the conductor layer surface was cut using a FIB (focused ion beam), and the thickness of the insulating layer between the conductor layers was measured from the cross-sectional SEM image. For each sample, cross-sectional SEM images of 5 randomly selected positions were observed, and the average value was used as the thickness of the insulating layer between the conductor layers (μm), which is shown in the following table.
[0304] (Measurement of insulation layer resistance)
[0305] The circular conductor side of the evaluation substrate obtained above with a diameter of 10 mm was used as the + electrode, and the grid conductor (copper) side of the inner layer circuit substrate connected to the pad with a diameter of 1 mm was used as the - electrode. The insulation resistance value after 200 hours at a temperature of 130°C, a relative humidity of 85%, and a DC voltage of 3.3 V was measured using a highly accelerated life tester ("PM422" manufactured by ETAC) and an electrochemical migration tester ("ECM-100" manufactured by J-RAS). This measurement was performed 6 times, and the resistance values of all 6 test samples were 1.0×10 7 The case with a resistance value of less than 1.0×10 7 The case where the insulation resistance was greater than Ω was evaluated as "×", and the evaluation results were shown in the following table together with the insulation resistance values. The lowest resistance value described in the following Table 1 is the lowest value of the insulation resistance values of the six test samples.
[0306] <Test Example 2: Evaluation of Warpage>
[0307] (1) Lamination of resin composition layers
[0308] The resin sheet C prepared in Preparation Example 3 was cut into a size of 14 cm square and laminated on one side of a substrate of a glass cloth-based epoxy resin double-sided copper-clad laminate (copper foil thickness of 3 μm, substrate thickness of 0.15 mm, "HL832NSF LCA" manufactured by Mitsubishi Gas Chemical Co., Ltd., size of 255×340 mm) cut into a size of 15 cm square using an intermittent vacuum pressure laminator (Nikko-Materials, 2-stage stacking laminator, CVP700);
[0309] For lamination, the pressure was reduced to 13 hPa or less for 30 seconds, and then pressure bonding was performed at 120° C. and 0.74 MPa for 30 seconds to prepare a substrate with a resin composition layer, and then the PET film was peeled off.
[0310] (2) Curing of the resin composition layer
[0311] The four sides of the substrate with the resin composition layer obtained in (1) were attached to a 1 mm thick SUS plate using polyimide tape so that the resin composition layer became the upper surface, and the resin composition layer was cured at 190° C. for 90 minutes.
[0312] (3) Determination of warpage
[0313] The polyimide tapes on three of the four sides of the substrate with the resin composition layer obtained in (2) above were peeled off, and the height from the SUS plate to the highest point was obtained, thereby obtaining the warpage value. In addition, the case where the warpage size is less than 1 cm is evaluated as "0", the case where it is more than 1 cm and less than 3 cm is evaluated as "△", and the case where it is more than 3 cm is evaluated as "×".
[0314] <Test Example 3: Evaluation of Copper Foil Adhesion (Peel Strength)>
[0315] (1) Base treatment of copper foil
[0316] The shiny surface of copper foil "3EC-III (thickness 35 μm)" manufactured by Mitsui Mining & Smelting Co., Ltd. was immersed in MECetchBOND "CZ-8101" manufactured by MEC Corporation, and the copper surface was roughened (Ra value = 1 μm) and rust-proofed (CL8300). This copper foil is called CZ copper foil. Furthermore, it was heated in an oven at 130°C for 30 minutes.
[0317] (2) Copper foil lamination and insulation layer formation
[0318] The following lamination treatment is performed: using an intermittent vacuum pressurized laminator (manufactured by Nikko-Materials, a 2-stage stacking laminator, CVP700), the resin sheet B prepared in Preparation Example 2 is laminated on both sides of the inner layer circuit substrate in such a manner that the resin composition layer is bonded to the inner layer circuit substrate. The lamination treatment is performed in the following manner: decompression is performed for 30 seconds to make the air pressure below 13 hPa, and then, crimping is performed at 100°C and a pressure of 0.74 MPa for 30 seconds. The PET film as a support is peeled off from the laminated resin composition layer. Under the same conditions as above, the treated surface of the CZ copper foil of "3EC-III" is laminated on the resin composition layer. Then, under the curing conditions of 190°C and 90 minutes, the resin composition layer is cured to form an insulating layer, thereby preparing a sample.
[0319] (3) Measurement of copper foil peel strength (adhesion) before accelerated environmental test (HAST)
[0320] The sample prepared above was cut into small pieces of 150×30 mm. A cutter was used to form a cut with a width of 10 mm and a length of 100 mm on the copper foil portion of the small piece, and one end of the copper foil was peeled off and clamped with a clamp (manufactured by TSE Co., Ltd., AUTO COM type tester "AC-50C-SL"), and the load when peeled off 35 mm in the vertical direction at a speed of 50 mm / min at room temperature was measured according to JIS C6481 using an Instron universal testing machine, and the result was taken as the pre-HAST peel strength (kgf / cm).
[0321] (4) Measurement of copper foil peel strength (adhesion) after accelerated environmental test (HAST)
[0322] Using a highly accelerated life tester ("PM422" manufactured by ETAC), the samples prepared above were subjected to 200 hours at a temperature of 130°C, a relative humidity of 85%, and a DC voltage of 3.3V. Then, one end of the copper foil was peeled off and clamped with a fixture (manufactured by TSE Co., Ltd., AUTO COM type tester "AC-50C-SL"), and an Instron universal tester was used. At room temperature, according to JIS C6481, the load when 35 mm was peeled off in the vertical direction at a speed of 50 mm / min was measured as the post-HAST peel strength (kgf / cm). It should be noted that the post-HAST peel strength greater than 0.35 kgf / cm was evaluated as "0", and the case of less than 0.35 kgf / cm was evaluated as "×".
[0323] <Test Example 4: Evaluation of plating adhesion>
[0324] (1) Base treatment of inner layer circuit board
[0325] A glass cloth-based epoxy resin double-sided copper-clad laminate (copper foil thickness 18 μm, substrate thickness 0.4 mm, R1515A manufactured by Panasonic) with an inner layer circuit formed thereon was etched 1 μm on both sides using CZ8101 manufactured by MEC to roughen the copper surface.
[0326] (2) Lamination of resin sheets with support
[0327] The protective film was peeled off from the resin sheet B prepared in Preparation Example 2 and laminated on both sides of the inner layer circuit board using an intermittent vacuum pressurization laminator (Nikko-Materials, 2-stage stacking laminator, CVP700). Lamination was performed by reducing the pressure for 30 seconds to make the air pressure below 13 hPa, and pressing at 130°C and 0.74 MPa for 45 seconds. Then, hot pressing was performed at 120°C and 0.5 MPa for 75 seconds.
[0328] (3) Curing of resin composition
[0329] The laminated resin composition layer was cured under curing conditions of 130° C. for 30 minutes and then 170° C. for 30 minutes to form an insulating layer.
[0330] (4) Through-hole formation
[0331] A CO2 laser processing machine ("605GTWIII(-P)" manufactured by Mitsubishi Electric Corporation) was used to irradiate the insulating layer with laser light to form a plurality of through holes with a top diameter (diameter) of about 30 μm on the insulating layer. The laser irradiation conditions were: mask diameter of 1 mm, pulse width of 16 μs, energy of 0.2 mJ / shot, number of shots of 2, and burst mode (10 kHz).
[0332] (5) Roughening treatment
[0333] The inner layer circuit board with the insulating layer formed thereon was immersed in Swelling Dip Securiganth P (glycol ethers, aqueous solution of sodium hydroxide) containing diethylene glycol monobutyl ether manufactured by Atotech Japan as a swelling solution at 60°C for 10 minutes, then immersed in Concentrate Compact P (aqueous solution of KMnO4: 60 g / L, NaOH: 40 g / L) manufactured by Atotech Japan as a roughening solution at 80°C for 20 minutes, and finally immersed in Reduction Solution Securiganth P (aqueous solution of sulfuric acid) manufactured by Atotech Japan as a neutralizing solution at 40°C for 5 minutes, and then dried at 80°C for 30 minutes. This substrate was designated as "evaluation substrate A".
[0334] (6) Plating using the semi-additive method
[0335] Evaluation substrate A was immersed in an electroless plating solution containing PdCl2 at 40°C for 5 minutes, and then immersed in an electroless copper plating solution at 25°C for 20 minutes. After heating at 150°C for 30 minutes and annealing, a resist layer was formed. After patterning by etching, copper sulfate electrolytic plating was performed to form a conductor layer with a thickness of 20 μm. Next, annealing was performed at 200°C for 60 minutes. This substrate was referred to as "evaluation substrate B".
[0336] (7) Measurement of peel strength (adhesion) of plated conductor layer
[0337] A cut with a width of 10 mm and a length of 100 mm was formed on the conductor layer of the evaluation substrate B, one end of the cut was peeled off and clamped with a clamp (TSE Co., Ltd., AUTO COM tester AC-50C-SL), and the load when 35 mm was peeled off in the vertical direction at a speed of 50 mm / min was measured at room temperature as the coating peeling strength (kgf / cm).
[0338] <Test Example 5: Evaluation of small-diameter through-hole formability>
[0339] For the roughened substrate A obtained in step (4) of Test Example 1, a through hole formed on an insulating layer having a thickness of 10 μm after roughening treatment was observed using a scanning electron microscope (S-4800 manufactured by Hitachi High-Technologies Co., Ltd.). Furthermore, the arbitrary diameter 2L of the circular opening surface of the through hole after roughening treatment was measured from the observed SEM image. 1t , the diameter 2L perpendicular to it 2t , substitute the top area S t =πL1t L 2t Calculate the top area S t . Top area S t The calculation is performed on the through holes at 5 randomly selected locations. The average top area of the through holes at the 5 locations is taken as the average top area S ta .
[0340] Similarly, the arbitrary diameter 2L of the circular bottom surface of the through hole after the roughening treatment is measured. 1b , the diameter 2L perpendicular to it 2b , substitute the bottom area S b =πL 1b L 2b Calculate the bottom area S b . The bottom area S b The calculation of is also performed on the through holes at 5 randomly selected positions. The bottom area S of the through holes at the 5 positions is b The average bottom area S ba .
[0341] The average top area S obtained above ta and the average bottom area S ba , calculate the average area ratio (average bottom area S ba With the average top area S ta The ratio of "S ba / S ta ”). The average area ratio S ba / S ta When the area ratio is 60% or more, it is judged as "0", and the average area ratio S ba / S ta The case where the area ratio is 50% or more and less than 60% is judged as "△", and the average area ratio S ba / S ta The case of less than 50% was judged as "×".
[0342] The amounts of nonvolatile components used in the resin compositions of Examples and Comparative Examples, the measurement results of Test Examples, the evaluation results, and the like are shown in Table 1 below.
[0343] [Table 1]
[0344]
[0345] It is known that by using the following resin composition, the warping of the cured product can be suppressed, and excellent insulation reliability, adhesion, and small-diameter through-hole formation can be achieved, wherein the resin composition is a resin composition comprising (A) an epoxy resin, (B) an inorganic filler, and (C) a granular or non-granular elastomer, wherein the specific surface area of the component (B) is 10 m 2 / g or more, the content of the (C) component is 35 mass % or less, and the average particle size of the (C) component is 0.8 μm or less.
Claims
1. A resin composition comprising: (A) Epoxy resin; (B) Inorganic filling materials; (C) polyurethane rubber particles, or non-granular elastomers; and (D) a curing agent, in, (B) component is silicon dioxide, The specific surface area of component (B) is 10m 2 / g or above, When the nonvolatile component in the resin composition is 100 mass %, the content of the component (B) is 40 mass % or more and 80 mass % or less, When the non-volatile components other than the inorganic filler in the resin composition are set to 100% by mass, the content of the component (C) is 35% by mass or less. When the component (C) is polyurethane rubber particles, the average particle size of the component (C) is 0.1 μm or less. When the component (C) is a non-granular elastomer, the non-granular elastomer is a flexible resin having at least one structure selected from a polybutadiene structure, a polysiloxane structure, a poly(meth)acrylate structure, a polyalkylene structure, a polyalkyleneoxy structure, a polyisoprene structure, a polyisobutylene structure, and a polycarbonate structure in the molecule.
2. A resin composition comprising: (A) Epoxy resin; (B) Inorganic filling materials; (C) polyurethane rubber particles, or non-granular elastomers; and (D) a curing agent, in, (B) component is silicon dioxide, The specific surface area of component (B) is 15 m 2 / g or more and 100m 2 / g or less, When the nonvolatile component in the resin composition is 100 mass %, the content of the component (B) is 10 mass % or more and 95 mass % or less, When the non-volatile components other than the inorganic filler in the resin composition are set to 100% by mass, the content of the component (C) is 35% by mass or less. When the component (C) is polyurethane rubber particles, the average particle size of the component (C) is 0.1 μm or less. When the component (C) is a non-granular elastomer, the non-granular elastomer is a flexible resin having at least one structure selected from a polybutadiene structure, a polysiloxane structure, a poly(meth)acrylate structure, a polyalkylene structure, a polyalkyleneoxy structure, a polyisoprene structure, a polyisobutylene structure, and a polycarbonate structure in the molecule.
3. The resin composition according to claim 1 or 2, wherein The specific surface area of component (B) is 20 m 2 / g or above.
4. The resin composition according to claim 1, wherein The specific surface area of component (B) is 500 m 2 / g or less.
5. The resin composition according to claim 1 or 2, wherein The specific surface area of component (B) is 25 m 2 / g or less.
6. The resin composition according to claim 1 or 2, wherein When the nonvolatile components other than the inorganic filler in the resin composition are taken as 100% by mass, the content of the component (A) is 90% by mass or less.
7. The resin composition according to claim 1 or 2, wherein When the nonvolatile components other than the inorganic filler in the resin composition are taken as 100% by mass, the content of the component (A) is 50% by mass or less.
8. The resin composition according to claim 1 or 2, wherein When the nonvolatile components other than the inorganic filler in the resin composition are taken as 100% by mass, the content of the component (A) is 10% by mass or more.
9. The resin composition according to claim 1 or 2, wherein When the nonvolatile components other than the inorganic filler in the resin composition are taken as 100% by mass, the content of the component (A) is 35% by mass or more.
10. The resin composition according to claim 1 or 2, wherein When the nonvolatile matter in the resin composition is 100% by mass, the content of the component (B) is 70% by mass or less.
11. The resin composition according to claim 2, wherein When the nonvolatile matter in the resin composition is 100% by mass, the content of the component (B) is 40% by mass or more.
12. The resin composition according to claim 1 or 2, wherein When the nonvolatile components other than the inorganic filler in the resin composition are taken as 100% by mass, the content of the component (C) is 25% by mass or less.
13. The resin composition according to claim 1 or 2, wherein When the nonvolatile components other than the inorganic filler in the resin composition are taken as 100% by mass, the content of the component (C) is 0.1% by mass or more.
14. The resin composition according to claim 1 or 2, wherein When the nonvolatile components other than the inorganic filler in the resin composition are taken as 100% by mass, the content of the component (C) is 1% by mass or more.
15. The resin composition according to claim 1 or 2, wherein When the nonvolatile components other than the inorganic filler in the resin composition are taken as 100% by mass, the content of the component (C) is 5% by mass or more.
16. The resin composition according to claim 1 or 2, wherein Component (C) is a non-granular elastomer, The non-granular elastomer includes a non-granular elastomer having a functional group capable of reacting with the component (A).
17. The resin composition according to claim 1 or 2, wherein The component (C) is polyurethane rubber particles.
18. The resin composition according to claim 1 or 2, wherein The component (C) is polyurethane rubber particles, and the average particle size of the component (C) is 0.005 μm or more.
19. The resin composition according to claim 1 or 2, wherein The component (C) is polyurethane rubber particles, and the average particle size of the component (C) is 0.05 μm or more.
20. The resin composition according to claim 1 or 2, wherein The non-particulate elastomer comprises a polybutadiene resin.
21. The resin composition according to claim 20, wherein The non-granular elastomer includes at least one selected from a polybutadiene resin containing a phenolic hydroxyl group and a polybutadiene resin containing an epoxy group.
22. The resin composition according to claim 1 or 2, wherein The component (D) contains an active ester-based curing agent.
23. The resin composition according to claim 1 or 2, wherein When the nonvolatile components other than the inorganic filler in the resin composition are taken as 100% by mass, the content of the component (D) is 80% by mass or less.
24. The resin composition according to claim 1 or 2, wherein When the nonvolatile components other than the inorganic filler in the resin composition are taken as 100% by mass, the content of the component (D) is 50% by mass or less.
25. The resin composition according to claim 1 or 2, wherein When the nonvolatile components other than the inorganic filler in the resin composition are taken as 100% by mass, the content of the component (D) is 1% by mass or more.
26. The resin composition according to claim 1 or 2, wherein When the nonvolatile components other than the inorganic filler in the resin composition are taken as 100% by mass, the content of the component (D) is 30% by mass or more. 27 . A cured product, which is a cured product of the resin composition according to claim 1 .
28. A sheet-like laminated material comprising the resin composition according to any one of claims 1 to 26.
29. A resin sheet comprising: Support body, and A resin composition layer formed from the resin composition according to any one of claims 1 to 26 and provided on the support. 30 . A printed wiring board comprising an insulating layer formed from a cured product of the resin composition according to claim 1 .
31. A semiconductor device comprising the printed wiring board according to claim 30.
Citation Information
Patent Citations
Silicone-containing polyimide resin, silicone-containing polyamic acid and their production
JP2000319386A
Polyimidesilicone resin, solution composition thereof, and polyimidesilicone resin coating film
JP2002012667A
Thermosetting resin composition containing modified polyimide resin
JP2006037083A
Resin composition
JP2016027097A
Resin composition
JP2019038969A